Oriented film for transferring liquid crystal compound orientation layer
Patent Information
- Application Number
- JP2024155516
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-01-07
- Filing Date
- 2024-09-10
- Publication Date
- 2025-03-27
AI Technical Summary
Existing methods for transferring liquid crystal compound alignment layers face challenges with stretched films like biaxially oriented polyester, which suffer from misalignment, light leakage, increased haze, and foreign matter due to heat shrinkage and ester cyclic trimers, making evaluation and production inefficient.
The use of a stretched polyester film with controlled angles and heat shrinkage rates, along with measures to minimize ester cyclic trimer precipitation, ensures accurate alignment and reduces haze and foreign matter, allowing for effective evaluation and transfer of retardation and polarizing layers.
This approach enables precise alignment and evaluation of retardation and polarizing layers on stretched films, preventing light leakage and improving production efficiency by maintaining designed orientations and reducing defects.
Abstract
Description
[Technical field]
[0001] The present invention relates to a transfer film for transferring a liquid crystal compound alignment layer, and more particularly to a transfer film for transferring a liquid crystal compound alignment layer, which is used when producing a polarizing plate or a retardation plate such as a circular polarizing plate having a retardation layer formed of a liquid crystal compound alignment layer laminated thereon, or when producing a polarizing plate having a polarizing layer formed of a liquid crystal compound alignment layer. [Background technology]
[0002] Conventionally, in image display devices, a circular polarizing plate is arranged on the panel surface of the image display panel facing the viewer in order to reduce reflection of external light. This circular polarizing plate is composed of a laminate of a linear polarizing plate and a retardation film such as λ / 4, and external light toward the panel surface of the image display panel is converted into linearly polarized light by the linear polarizing plate, and then converted into circularly polarized light by the retardation film such as λ / 4. When the circularly polarized external light is reflected on the surface of the image display panel, the rotation direction of the polarization plane is reversed, and this reflected light is conversely converted into linearly polarized light in the direction blocked by the linear polarizing plate by the retardation film such as λ / 4, and then blocked by the linear polarizing plate, so that emission to the outside is suppressed. In this way, a circular polarizing plate in which a retardation film such as λ / 4 is bonded to a polarizing plate is used.
[0003] As the retardation film, a single retardation film such as a cyclic olefin (see Patent Document 1), a polycarbonate (see Patent Document 2), or a stretched film of triacetyl cellulose (see Patent Document 3) is used. As the retardation film, a laminated retardation film having a retardation layer made of a liquid crystal compound on a transparent film (see Patent Documents 4 and 5) is used. In the above, it is described that when a retardation layer made of a liquid crystal compound is provided, the liquid crystal compound may be transferred.
[0004] In addition, a method for producing a retardation film by transferring a retardation layer made of a liquid crystal compound onto a transparent film is known in Patent Document 6, etc. A method is also known in which a retardation layer made of a liquid crystal compound such as λ / 4 is provided on a transparent film by such a transfer method to produce a λ / 4 film (see Patent Documents 7 and 8).
[0005] In these transfer methods, various materials have been introduced as the substrate for transfer, and among them, many transparent resin films such as polyester, triacetyl cellulose, cyclic polyolefin, etc. Unstretched films such as triacetyl cellulose and cyclic polyolefin are preferable because they have no birefringence and can inspect (evaluate) the state of the retardation layer in a state where the retardation layer is provided on the film substrate, but these films are not necessarily optimal because they are expensive and have poor mechanical strength when made thin.
[0006] On the other hand, stretched films have superior mechanical strength compared to unstretched films and are preferred as film substrates for transfer, but because they have birefringence, it has been difficult to evaluate the retardation layer. In particular, biaxially stretched polyester films are relatively inexpensive and have superior mechanical strength and heat resistance, making them very preferred as film substrates for transfer, but because polyester films have large birefringence, it has been difficult to evaluate the retardation layer in a state where a liquid crystal compound alignment layer (retardation layer) is laminated on the film substrate.
[0007] Therefore, when evaluating the retardation layer in a stretched film, it was necessary to evaluate it after transferring it to an object (another transparent resin film, a polarizing plate, etc.), to peel off the retardation layer and evaluate only the retardation layer, or to transfer it to glass or the like and evaluate it. In the method of evaluating after transferring it to an object, if there was a problem with the retardation layer, it was necessary to dispose of it as a non-standard product including the polarizing plate, which was a normal product, as a result, and this was inferior in productivity. The method of evaluating after peeling off the retardation layer had the problem that it could not be evaluated if the retardation layer became thin. In addition, the method of evaluating after peeling off or the method of transferring to glass required a sample extraction evaluation, and it was not possible to evaluate the entire amount.
[0008] In addition, stretched films have superior mechanical strength compared to unstretched films and are preferable as film substrates for transfer, but the orientation direction of the transferred retardation layer is not aligned as designed, and there are often problems with deviation from the designed orientation. When a polarizing plate having a retardation with an orientation direction that is deviated from the designed orientation is used in a display, problems such as light leakage may occur. In particular, stretched polyester films such as biaxially stretched polyester films are relatively inexpensive and have excellent mechanical strength and heat resistance, and are very preferable as film substrates for transfer in these respects, but the deviation from the designed orientation and the resulting light leakage problems are particularly prominent in polyester films.
[0009] Furthermore, polyester films such as biaxially oriented polyester films are relatively inexpensive and have excellent mechanical strength and heat resistance, and from these points they are very preferable as film substrates for transfer, but when a polyester film is used as a film substrate for transfer, there are problems in that the haze of the film increases and foreign matter is generated in the film during the process of forming a retardation layer (liquid crystal compound alignment layer) thereon to produce a laminate. Furthermore, there is a problem in that such increased haze and foreign matter disrupt the polarization during irradiation with ultraviolet light to control the alignment of the liquid crystal compound, resulting in a failure to achieve the alignment direction as designed.
[0010] In addition, a method for producing a polarizing plate by transferring a polarizing layer (liquid crystal compound alignment layer) containing a liquid crystal compound and a dichroic dye laminated on a transfer film to a protective film has also been known, but this method also has the same problems as those described above. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2012-56322 A [Patent Document 2] JP 2004-144943 A [Patent Document 3] JP 2004-46166 A [Patent Document 4] JP 2006-243653 A [Patent Document 5] JP 2001-4837 A [Patent Document 6] Japanese Patent Application Publication No. 4-57017 [Patent Document 7] JP 2014-071381 A [Patent Document 8] JP 2017-146616 A Summary of the Invention [Problem to be solved by the invention]
[0012] The present invention has been made against the background of the problems of the conventional techniques. That is, the first object of the present invention is to provide a transfer film for transferring a liquid crystal compound alignment layer, which uses an inexpensive stretched film such as polyester having excellent mechanical strength as a transfer film, and which allows evaluation of the alignment state of a liquid crystal compound alignment layer (retardation layer or polarizing layer) provided on the transfer film even in a state where the layer is laminated on the transfer film.
[0013] A second object of the present invention is to provide a transfer film for transferring a liquid crystal compound alignment layer, which uses an inexpensive stretched film such as polyester, which has excellent mechanical strength, as a transfer film, while reducing the problem of deviation in the alignment direction of the transferred retardation layer or polarizing layer, allowing the retardation layer or polarizing layer to be transferred with the designed alignment, thereby preventing the problem of light leakage from the display.
[0014] The third object of the present invention is to provide a transfer film that uses an inexpensive stretched film such as polyester, which has excellent mechanical strength, as a transfer film for transferring a liquid crystal compound alignment layer, while effectively preventing an increase in film haze and the generation of foreign matter in the film during the process of forming a retardation layer or a polarizing layer (liquid crystal compound alignment layer) on the film, and that can form a retardation layer or a polarizing layer (liquid crystal compound alignment layer) with the designed orientation. [Means for solving the problem]
[0015] As a result of intensive research into achieving the first object, the present inventors have found that by using an alignment film in which the angle between its alignment direction and the flow direction of the alignment film or the direction perpendicular to the flow direction is controlled to be equal to or less than a specific angle even at the point where it is at a maximum, the above-mentioned conventional problems do not arise and the retardation phase can be well evaluated even when a liquid crystal compound alignment layer is laminated on an alignment film.
[0016] In order to achieve the second object, the present inventors have investigated the reason why the orientation direction of the transferred retardation layer or polarizing layer does not match the designed orientation direction when a conventional stretched film is used as a film substrate for transfer. As a result, the inventors have found that the stretched film substrate is thermally shrunk to some extent by heat treatment when a liquid crystal compound is oriented on the stretched film substrate to form a retardation layer or polarizing layer, but the degree of this thermal shrinkage is significantly different in two orthogonal directions of the stretched film, so that the substrate film after thermal shrinkage is distorted, and that this distortion adversely affects the orientation direction of the retardation layer or polarizing layer formed on the substrate film, so that the orientation direction of the retardation layer or polarizing layer deviates from the designed orientation direction. The inventors have conducted extensive research into methods for effectively preventing this distortion of the base film, and have found that, even if there is variation in the thermal shrinkage rate of the film between the flow direction (MD) and the direction perpendicular to the flow direction (TD), by using an oriented film as the base film in which the difference is controlled within a specific range, the above-mentioned conventional problems do not occur, and the retardation layer and polarizing layer can be transferred with the designed orientation, and the problem of light leakage does not occur.
[0017] In order to achieve the third object, the present inventors have investigated the causes of an increase in the haze of a film or the generation of foreign matter in a film when a conventional stretched polyester film is used as a film substrate for transfer in the process of forming a retardation layer or a polarizing layer (liquid crystal compound alignment layer) on the film. As a result, the inventors have found that the polyester resin constituting the polyester film necessarily contains ester cyclic trimers (oligomers) as a by-product of the reaction during polymerization in the manufacturing process, and therefore, when a polyester film is used as a substrate film for transfer, these oligomers precipitate on the surface of the substrate film by the heat treatment in the process of applying a liquid crystal compound thereon and heating to form a liquid crystal compound alignment layer (retardation layer or polarizing layer), resulting in an increase in haze or the generation of foreign matter. The present inventors have conducted extensive research into methods for effectively preventing such an increase in haze and the generation of foreign matter during the heat treatment of a transfer oriented polyester film, and have found that by using a polyester film in which the amount of oligomer precipitation is controlled within a specific range, it is possible to form a retardation layer or a polarizing layer (liquid crystal compound orientation layer) that is oriented as designed without the above-mentioned conventional problems occurring.
[0018] That is, the invention for achieving the first object has the following configurations (1) to (6). (1) An alignment film for transferring an alignment layer of a liquid crystal compound to an object, characterized in that the angle between the orientation direction of the alignment film and the flow direction of the alignment film or a direction perpendicular to the flow direction is 14 degrees or less as the maximum value of values measured at five locations: both ends 5 cm inward from each end in the width direction of the film, the center, and a middle portion halfway between the center and both ends. (2) The alignment film for transferring an alignment layer for a liquid crystal compound according to (1), wherein the difference in the orientation angle in the width direction of the alignment film is 7 degrees or less. (3) The alignment film for transferring an alignment layer of a liquid crystal compound according to (1) or (2), wherein the alignment film is a polyester film. (4) A laminate for transferring a liquid crystal compound alignment layer, comprising a liquid crystal compound alignment layer and an alignment film, the alignment film being the alignment film described in any one of (1) to (3). (5) A method for producing a liquid crystal compound alignment layer laminated polarizing plate, comprising the steps of: bonding a polarizing plate to a liquid crystal compound alignment layer surface of the laminate described in (4) to form an intermediate laminate; and peeling the alignment film from the intermediate laminate. (6) A method for inspecting the orientation state of a liquid crystal compound alignment layer in the laminate described in (4), comprising the steps of irradiating the alignment film surface of the laminate with linearly polarized light having an electric field oscillation direction parallel to the alignment direction of the alignment film, or a direction perpendicular to the alignment direction, or a flow direction of the alignment film, or a direction perpendicular to the flow direction, and receiving the light on the liquid crystal compound alignment layer surface side.
[0019] The invention to achieve the second object has the following configurations (1) to (6). (1) An alignment film for transferring a liquid crystal compound alignment layer to an object, characterized in that the difference between the heat shrinkage rate at 150°C for 30 minutes in the machine direction of the alignment film and the heat shrinkage rate at 150°C for 30 minutes in the direction perpendicular to the machine direction of the alignment film is 4% or less. (2) The alignment film for transferring a liquid crystal compound alignment layer according to (1), characterized in that the difference between the heat shrinkage rate at 150°C for 30 minutes in a direction at 45 degrees to the flow direction of the alignment film and the heat shrinkage rate at 150°C for 30 minutes in a direction at 135 degrees to the flow direction of the alignment film is 4% or less. (3) The alignment film for transferring an alignment layer of a liquid crystal compound according to (1) or (2), wherein the alignment film is a polyester film. (4) A laminate for transferring a liquid crystal compound alignment layer, comprising a liquid crystal compound alignment layer and an alignment film, the alignment film being the alignment film described in any one of (1) to (3). (5) A method for producing a liquid crystal compound alignment layer laminated polarizing plate, comprising the steps of: bonding a polarizing plate to a liquid crystal compound alignment layer surface of the laminate described in (4) to form an intermediate laminate; and peeling the alignment film from the intermediate laminate. (6) A method for inspecting the orientation state of a liquid crystal compound alignment layer in the laminate described in (4), comprising the steps of irradiating the alignment film surface of the laminate with linearly polarized light having an electric field oscillation direction parallel to the alignment direction of the alignment film, or a direction perpendicular to the alignment direction, or a flow direction of the alignment film, or a direction perpendicular to the flow direction, and receiving the light on the liquid crystal compound alignment layer surface side.
[0020] The invention to achieve the third object has the following configurations (1) to (6). (1) An oriented polyester film for transferring a liquid crystal compound alignment layer to an object, in which the amount of ester cyclic trimer precipitated on the release surface of the oriented polyester film after heating at 150°C for 90 minutes is 1.0 mg / m 2 An oriented polyester film for transferring an orientation layer for a liquid crystal compound, characterized in that: (2) The oriented polyester film for transferring a liquid crystal compound alignment layer according to (1), characterized in that the content of ester cyclic trimer in the polyester resin constituting the release side layer of the oriented polyester film is 0.7 mass % or less. (3) The oriented polyester film for transferring an alignment layer for liquid crystal compounds according to (1) or (2), wherein a coating layer for preventing precipitation of an ester cyclic trimer is provided on the release surface of the oriented polyester film. (4) A laminate for transferring a liquid crystal compound alignment layer, comprising a liquid crystal compound alignment layer and an oriented polyester film, the oriented polyester film being the oriented polyester film described in any one of (1) to (3). (5) A method for producing a liquid crystal compound alignment layer laminated polarizing plate, comprising the steps of: bonding a polarizing plate and a liquid crystal compound alignment layer surface of the laminate described in (4) to form an intermediate laminate; and peeling off the oriented polyester film from the intermediate laminate. (6) A method for inspecting the orientation state of a liquid crystal compound orientation layer in the laminate described in (4), comprising the steps of irradiating the oriented polyester film surface of the laminate with linearly polarized light having an electric field vibration direction parallel to the orientation direction of the oriented polyester film, or a direction perpendicular to the orientation direction, or a flow direction of the oriented polyester film, or a direction perpendicular to the flow direction, and receiving the light on the liquid crystal compound orientation layer surface side. Effect of the Invention
[0021] According to the first invention, while using an inexpensive stretched film such as polyester, which has excellent mechanical strength, the orientation state of a liquid crystal compound orientation layer (retardation layer or polarizing layer) provided on the orientation film can be evaluated even when laminated on the orientation film.
[0022] According to the second invention, a retardation layer or a polarizing layer can be transferred with the designed orientation while using a stretched film such as polyester, which is inexpensive and has excellent mechanical strength, and the problem of light leakage in the display can be prevented.
[0023] According to the third invention, while using an inexpensive stretched polyester film having excellent mechanical strength, it is possible to effectively prevent an increase in haze and the generation of foreign matter during heat treatment of the film, so that a retardation layer or a polarizing layer (liquid crystal compound alignment layer) having the designed orientation can be formed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The alignment film of the first invention is intended for transferring a liquid crystal compound alignment layer to an object (another transparent resin film, a polarizing plate, etc.), and is characterized in that the angle between the alignment direction of the alignment film and the flow direction of the alignment film or a direction perpendicular to the flow direction is 14 degrees or less at the maximum point.
[0025] The alignment film of the second invention is intended for transferring a liquid crystal compound alignment layer to an object (another transparent resin film, a polarizing plate, etc.), and is characterized in that the difference between the heat shrinkage rate at 150°C for 30 minutes in the machine direction (MD) of the alignment film and the heat shrinkage rate at 150°C for 30 minutes in the direction perpendicular to the machine direction of the alignment film (TD) is 4% or less.
[0026] The oriented polyester film of the third invention is intended for transferring a liquid crystal compound orientation layer to an object (another transparent resin film, a polarizing plate, etc.), and the amount of ester cyclic trimer precipitated on the release surface of the oriented polyester film after heating at 150°C for 90 minutes is 1.0 mg / m 2 The oriented polyester film is characterized by the following. Hereinafter, the oriented polyester film may be simply referred to as an oriented film. In addition, when an oligomer block coating layer, a release layer, a flattening coating layer, a slippery coating layer, an antistatic coating layer, etc. are provided, the oriented polyester film or the oriented film may include these layers.
[0027] The resin used for the oriented film is preferably one having birefringence, more preferably polyester, polycarbonate, polystyrene, polyamide, polypropylene, cyclic polyolefin, or triacetyl cellulose, further preferably polyester, and particularly preferably polyethylene terephthalate.
[0028] The oriented film may be a single layer or a multi-layer structure by coextrusion. In the case of a multi-layer structure, examples include a surface layer (a release layer A) / back layer (B), an A / middle layer (C) / A (the release layer and the back layer are the same), an A / C / B, etc.
[0029] When stretching a film, uniaxial stretching, weak biaxial stretching (stretched in two axial directions but weak in one direction), or biaxial stretching may be used, but uniaxial stretching or weak biaxial stretching is preferred because it allows the orientation direction to be constant over a wide range in the width direction. In the case of weak biaxial stretching, it is preferable to set the main orientation direction to the direction of stretching in the latter stage. In the case of uniaxial stretching, the stretching direction may be either the flow direction of the film production (machine direction) or the direction perpendicular to this (transverse direction). In the case of biaxial stretching, simultaneous biaxial stretching or sequential biaxial stretching may be used. Stretching in the longitudinal direction is preferably performed by a group of rolls having different speed differences, and stretching in the transverse direction is preferably performed by a tenter.
[0030] The transfer orientation film is industrially supplied in the form of a wound film roll. The lower limit of the roll width is preferably 30 cm, more preferably 50 cm, even more preferably 70 cm, particularly preferably 90 cm, and most preferably 100 cm. The upper limit of the roll width is preferably 5000 cm, more preferably 4000 cm, and even more preferably 3000 cm.
[0031] The lower limit of the roll length is preferably 100 m, more preferably 500 m, and even more preferably 1000 m. The upper limit of the roll length is preferably 100,000 m, more preferably 50,000 m, and even more preferably 30,000 m.
[0032] Generally, polarizers are made by stretching polyvinyl alcohol in the flow direction of the film and absorbing iodine or dichroic dyes made of organic compounds, and the extinction axis (absorption axis) of the polarizer is in the flow direction of the film. In the case of a circular polarizing plate, the slow axis (orientation direction) of the λ / 4 layer as a retardation layer is laminated at 45 degrees to the extinction axis, or the λ / 4 layer and the λ / 2 layer are laminated in an oblique direction (10 to 80 degrees). In addition, the optical compensation layer used in liquid crystal displays is also laminated in an oblique direction to the extinction axis of the polarizer.
[0033] Therefore, the orientation state of the retardation layer can be inspected (evaluated) by, for example, irradiating the retardation layer with linearly polarized light having a vibration direction parallel or perpendicular to the flow direction of the film from the transfer orientation film side, and detecting the light that has become elliptically polarized in the retardation layer with a light receiving element through a light receiving side retardation plate for returning the elliptically polarized light to linearly polarized light and a light receiving side polarizing plate installed in a direction that does not pass the linearly polarized light returned by the retardation plate. If the light that passes through the light receiving side retardation plate that becomes linearly polarized when the retardation and orientation direction are as designed for the retardation layer provided on the transfer orientation film is in an extinct state, it can be seen that the retardation layer is as designed. Conversely, if there is light leakage, it can be seen that it is deviated from the design.
[0034] However, if the orientation direction of the transfer orientation film is shifted from parallel (MD) or perpendicular (TD) to the flow direction of the orientation film, the linearly polarized light passing through the transfer orientation film becomes elliptically polarized light, causing light leakage and making it difficult to accurately evaluate the retardation layer. The present invention minimizes this shift, making it possible to accurately evaluate the retardation layer.
[0035] The lower limit of the angle (maximum point) between the MD or TD of the transfer alignment film of the present invention and the alignment direction is preferably 0 degrees. The upper limit of the angle between the MD or TD of the transfer alignment film of the present invention and the alignment direction is preferably 14 degrees at the maximum, more preferably 7 degrees, even more preferably 5 degrees, particularly preferably 4 degrees, and most preferably 3 degrees. If the angle exceeds the above, it may be difficult to evaluate the alignment state of the retardation layer (liquid crystal compound alignment layer).
[0036] The lower limit of the difference in the orientation angle across the entire width (width direction) of the alignment film for transfer of the present invention is preferably 0 degrees. The upper limit of the difference in the orientation angle across the entire width of the alignment film for transfer of the present invention is preferably 7 degrees, more preferably 5 degrees, even more preferably 3 degrees, and particularly preferably 2 degrees. If the difference exceeds the above range, it may be difficult to evaluate the alignment state of the retardation layer (liquid crystal compound alignment layer) in the width direction.
[0037] When stretching in the TD direction in a tenter, the film is subjected to a force that shrinks it in the MD direction in the stretching zone and heat setting zone. The ends of the film are fixed with clips, but the center is not fixed, so the bowing phenomenon occurs, where the film emerges late in a bow shape at the exit of the tenter. This causes distortion in the orientation direction.
[0038] In order to reduce the distortion in the orientation direction and achieve the above-mentioned properties, the stretching temperature, stretching ratio, stretching speed, heat setting temperature, temperature in the relaxation step, ratio in the relaxation step, temperature distribution in the width direction of each temperature, etc. may be appropriately adjusted.
[0039] In addition, if the orientation direction does not fall within the specified range over the entire width of the film produced, it is preferable to use a portion that falls within the above characteristic range, such as near the center of a stretched wide film. In addition, since the distortion in the orientation direction tends to decrease when the orientation in the uniaxial direction is strengthened, it is also a preferable method to use a weak biaxial or uniaxially stretched film. In particular, a weak biaxial or uniaxially stretched film in which the MD direction is the main orientation direction is preferable.
[0040] In the present invention, the angle between the orientation direction of the transfer orientation film and the flow direction of the oriented film or the direction perpendicular to the flow direction, and the angle difference between the orientation angles in the width direction of the film are determined as follows. First, the film was pulled out from the roll, and the orientation direction was determined at five points: both ends (5 cm inward from each end), the center, and the middle part between the center and both ends. The middle part between the center and both ends is located at a position that divides the distance between the center and both ends in half. The orientation direction was determined as the slow axis direction of the film determined using a molecular orientation meter. Next, it was examined whether the overall orientation direction of the film was close to the machine direction (MD) or the width direction (TD). Then, when the overall orientation direction of the film was close to the machine direction, the angle between the orientation direction and the machine direction of the film was determined at each of the above five points, and the value at the point where the angle was the largest was adopted as the maximum value of the "angle between the orientation direction of the oriented film and the machine direction of the oriented film". On the other hand, when the overall orientation direction of the film was close to the width direction, the angle between the orientation direction and the direction perpendicular to the machine direction of the film was determined at each of the above five points, and the value at the point where the angle was the largest was adopted as the maximum value of the "angle between the orientation direction of the oriented film and the direction perpendicular to the machine direction of the oriented film". Moreover, the difference between the maximum and minimum angles among the angles determined at the above five locations was defined as the "angle difference of the orientation angle in the width direction of the film." The angle is considered to be a positive value when the orientation direction is on the same side as the maximum value in the longitudinal or width direction, and a negative value when the orientation direction is on the opposite side to the longitudinal or width direction. The minimum value is evaluated by distinguishing between positive and negative.
[0041] The lower limit of the difference in heat shrinkage rate between the MD direction and the TD direction of the transfer orientation film of the present invention at 150°C for 30 minutes is preferably 0%. The upper limit of the difference in heat shrinkage rate between the MD direction and the TD direction of the transfer orientation film of the present invention at 150°C for 30 minutes is preferably 4%, more preferably 3%, even more preferably 2%, particularly preferably 1.5%, and most preferably 1%. If it exceeds the above range, when a high temperature is required for the alignment treatment of the liquid crystal compound or when multiple liquid crystal compounds are laminated and the temperature history is long, the alignment direction of the liquid crystal compound may deviate from the design, and light leakage may occur when the polarizing plate is used in a display.
[0042] The lower limit of the heat shrinkage rate in the MD direction of the transfer orientation film of the present invention at 150°C for 30 minutes is preferably -2%, more preferably -0.5%, even more preferably -0.1%, particularly preferably 0%, and most preferably 0.01%. If it is less than the above, it may be difficult to actually achieve the numerical value. In addition, the upper limit of the heat shrinkage rate in the MD direction of the transfer orientation film of the present invention at 150°C for 30 minutes is preferably 4%, more preferably 3%, even more preferably 2.5%, particularly preferably 2%, and most preferably 1.5%. If it exceeds the above, it may be difficult to adjust the difference in heat shrinkage rate. In addition, the flatness may be deteriorated, and the workability may be deteriorated.
[0043] The lower limit of the heat shrinkage rate in the TD direction of the transfer orientation film of the present invention at 150°C for 30 minutes is preferably -2%, more preferably -0.5%, even more preferably -0.1%, particularly preferably 0%, and most preferably 0.01%. If it is less than the above, it may be difficult to actually achieve the numerical value. In addition, the upper limit of the heat shrinkage rate in the TD direction of the transfer orientation film of the present invention at 150°C for 30 minutes is preferably 4%, more preferably 2.5%, even more preferably 2%, particularly preferably 1.5%, and most preferably 1%. If it exceeds the above, it may be difficult to adjust the difference in heat shrinkage rate. In addition, the flatness may be deteriorated, and the workability may be deteriorated.
[0044] The lower limit of the difference in the heat shrinkage rate at 150°C for 30 minutes in the direction of 45° to the MD direction and the direction of 135° to the MD direction of the transfer orientation film of the present invention is preferably 0%. If it is less than the above, it may be difficult to achieve the numerical value in reality. In addition, the upper limit of the difference in the heat shrinkage rate at 150°C for 30 minutes in the direction of 45° to the MD direction and the direction of 135° to the MD direction of the transfer orientation film of the present invention is preferably 4%, more preferably 3%, even more preferably 2%, particularly preferably 1.5%, and most preferably 1%. If it is out of the above range, the alignment direction of the liquid crystal compound may deviate from the design, and light leakage may occur when the polarizing plate is used in a display.
[0045] The heat shrinkage properties of the film can be adjusted by the stretching temperature, stretching ratio, heat setting temperature, relaxation step ratio, relaxation step temperature, etc. It is also preferable to release the film from the clips and wind it up when the surface temperature of the film is 100°C or higher during the cooling step. The film can be released from the clips by opening the clips or by cutting off the end held by the clips with a blade or the like. Offline heat treatment (annealing treatment) is also an effective method.
[0046] In order to achieve the above-mentioned heat shrinkage characteristics of the transfer orientation film of the present invention at 150° C. for 30 minutes, the material of the transfer orientation film is preferably polyester, particularly polyethylene terephthalate.
[0047] The lower limit of the maximum heat shrinkage at 95°C of the transfer orientation film of the present invention is preferably 0%, more preferably 0.01%. If it is less than the above, it may be difficult to achieve the numerical value in practice. In addition, the upper limit of the maximum heat shrinkage at 95°C of the transfer orientation film of the present invention is preferably 2.5%, more preferably 2%, even more preferably 1.2%, particularly preferably 1%, and most preferably 0.8%. If it exceeds the above, light leakage may occur when the polarizing plate is used in a display.
[0048] The lower limit of the angle between the maximum heat shrinkage direction of the transfer orientation film of the present invention and the MD or TD direction is preferably 0 degrees. The upper limit of the angle between the maximum heat shrinkage direction of the transfer orientation film of the present invention and the MD or TD direction is preferably 20 degrees, more preferably 15 degrees, even more preferably 10 degrees, particularly preferably 7 degrees, and most preferably 5 degrees. If the angle exceeds the above range, the alignment direction of the liquid crystal compound may deviate from the design, and light leakage may occur when the polarizing plate is used in a display.
[0049] The lower limit of the elastic modulus in the MD direction and the elastic modulus in the TD direction of the transfer orientation film of the present invention is preferably 1 GPa, more preferably 2 GPa. If it is less than the above, it may stretch during each process and may not be oriented in the designed direction. In addition, the upper limit of the elastic modulus in the MD direction and the elastic modulus in the TD direction of the transfer orientation film of the present invention is preferably 8 GPa, more preferably 7 GPa. If it exceeds the above, it may be difficult to achieve the numerical value in reality.
[0050] When the transfer orientation film of the present invention is a polyethylene terephthalate film, the lower limit of the amount of ester cyclic trimer precipitated on the surface of the release surface of the oriented polyester film after heating at 150° C. for 90 minutes (hereinafter referred to as the surface oligomer precipitate amount (150° C. 90 min)) is preferably 0 mg / m 2 and more preferably 0.01 mg / m 2 If the value is less than the above, it may be difficult to achieve the numerical value in practice. The upper limit of the surface oligomer precipitation amount (150°C 90 min) is preferably 1 mg / m 2 and more preferably 0.7 mg / m 2 and more preferably 0.5 mg / m 2 and particularly preferably 0.3 mg / m 2 If the above is exceeded, when multiple liquid crystal compound alignment layers are laminated or when alignment treatment at high temperatures is required, haze increases or foreign matter is generated, and polarization is disturbed during alignment control by ultraviolet irradiation, making it impossible to obtain a retardation layer or polarizing layer as designed. In the present invention, the "release surface" of the alignment film means the surface of the alignment film on which the liquid crystal compound alignment layer to be transferred by the alignment film is intended to be provided. When an oligomer block coat layer, a flattening coat layer, a release layer, or the like is provided, if a liquid crystal compound alignment layer is provided on top of this, the surfaces of these oligomer block coat layer, flattening layer, release layer, etc. (surfaces in contact with the liquid crystal compound alignment layer) are the "release surface" of the alignment film.
[0051] In order to reduce the amount of surface oligomer precipitation, it is preferable to provide a coating layer (oligomer block coating layer) that blocks the precipitation of oligomers (ester cyclic trimers) on the surface of the alignment film for transfer.
[0052] The oligomer block coat layer preferably contains 50% by weight or more of a resin having a Tg of 90° C. or more. Such resins are preferably amino resins such as melamine, alkyd resins, polystyrene, acrylic resins, etc. The upper limit of the Tg of the resin is preferably 200° C.
[0053] The lower limit of the thickness of the oligomer block coat layer is preferably 0.01 μm, more preferably 0.03 μm, and even more preferably 0.05 μm. If it is less than the above, sufficient blocking effect may not be obtained. The upper limit of the thickness of the oligomer block coat layer is preferably 10 μm, more preferably 5 μm, and even more preferably 2 μm. If it exceeds the above, the effect may become saturated.
[0054] In order to reduce the amount of surface oligomer precipitation, it is also preferable to reduce the content of oligomer (ester cyclic trimer) in the polyester resin constituting the release surface side layer of the transfer orientation film (hereinafter referred to as the surface layer oligomer content). The lower limit of the surface layer oligomer content is preferably 0.3 mass%, more preferably 0.33 mass%, and even more preferably 0.35 mass%. If it is less than the above, it may be difficult to achieve the numerical value in reality. The upper limit of the surface layer oligomer content is preferably 0.7 mass%, more preferably 0.6 mass%, and even more preferably 0.5 mass%. In the present invention, the "release surface side layer" of the orientation film means the layer in which the release surface exists among the polyester layers constituting the orientation film. Here, even when the film is a single layer, it may be called the release surface side layer. In this case, the back side layer and the release surface side layer described later are the same layer.
[0055] In order to reduce the surface oligomer content, it is preferable to reduce the oligomer content in the raw polyester. The lower limit of the oligomer content in the raw polyester is preferably 0.23% by mass, more preferably 0.25% by mass, and even more preferably 0.27% by mass. The upper limit of the oligomer content in the raw polyester is preferably 0.7% by mass, more preferably 0.6% by mass, and even more preferably 0.5% by mass. The oligomer content in the raw polyester can be reduced by subjecting the solid polyester to a heat treatment at a temperature of 180°C or higher and below the melting point, such as solid-phase polymerization. It is also preferable to deactivate the catalyst in the polyester.
[0056] In order to reduce the amount of oligomer precipitation on the surface layer, it is also effective to shorten the melting time during film formation.
[0057] When the transfer orientation film of the present invention is a polyester film, the lower limit of the intrinsic viscosity (IVf) of the polyester constituting the film is preferably 0.45 dl / g, more preferably 0.5 dl / g, and even more preferably 0.53 dl / g. If it is less than the above, the impact resistance of the film may be poor. Also, film formation may be difficult, and the thickness uniformity may be poor. The upper limit of IVf is preferably 0.9 dl / g, more preferably 0.8 dl / g, and even more preferably 0.7 dl / g. If it exceeds the above, the heat shrinkage rate may be high. Also, film formation may be difficult.
[0058] The lower limit of the light transmittance of the transfer alignment film of the present invention at a wavelength of 380 nm is preferably 0%. The upper limit of the light transmittance of the transfer alignment film of the present invention at a wavelength of 380 nm is preferably 20%, more preferably 15%, even more preferably 10%, and particularly preferably 5%. If it exceeds the above, when a specific alignment direction is achieved by irradiating polarized ultraviolet light, the directional uniformity of the alignment layer or liquid crystal compound alignment layer may deteriorate due to reflection from the back surface. The light transmittance at a wavelength of 380 nm can be kept within the range by adding a UV absorber.
[0059] The lower limit of the haze of the oriented film for transfer of the present invention is preferably 0.01%, more preferably 0.1%. If it is less than the above, it may be difficult to achieve the numerical value in practice. Furthermore, the upper limit of the haze of the oriented film for transfer of the present invention is preferably 3%, more preferably 2.5%, even more preferably 2%, and particularly preferably 1.7%. If it exceeds the above, the polarization may be disturbed during irradiation with polarized UV light, and the retardation layer or polarizing layer may not be obtained as designed. Furthermore, when inspecting the retardation layer or polarizing layer, light leakage may occur due to diffuse reflection, making the inspection difficult.
[0060] The lower limit of the haze of the orientation film for transfer of the present invention after heating at 150° C. for 90 minutes is the same as above.
[0061] The lower limit of the amount of change in haze of the orientation film for transfer of the present invention before and after heating at 150° C. for 90 minutes is preferably 0%, and the upper limit is preferably 0.5%, more preferably 0.4%, and even more preferably 0.3%.
[0062] In the transfer orientation film of the present invention, the lower limit of the refractive index nx in the slow axis direction - the refractive index ny in the fast axis direction is preferably 0.005, more preferably 0.01, even more preferably 0.02, particularly preferably 0.03, most preferably 0.04, and most preferably 0.05. If it is less than the above, it may be difficult to achieve the numerical value in reality. Moreover, the upper limit of nx-ny is preferably 0.15, more preferably 0.13, and even more preferably 0.12. If it exceeds the above, it may be difficult to achieve the numerical value in reality. In particular, in the case of a polyethylene terephthalate film, it is preferable that the value of nx-ny is as described above.
[0063] In the case of biaxial stretching, the lower limit of nx-ny is preferably 0.005, more preferably 0.01. If it is less than the above, it may be difficult to achieve the numerical value in reality. In addition, in the case of biaxial stretching, the upper limit of nx-ny is preferably 0.05, more preferably 0.04, and even more preferably 0.03. If it exceeds the above, it may be difficult to achieve the numerical value in reality.
[0064] In the case of uniaxial stretching, the lower limit of nx-ny is preferably 0.05, more preferably 0.06. If it is less than the above, the merits of uniaxial stretching may be diminished. In addition, in the case of uniaxial stretching, the upper limit of nx-ny is preferably 0.15, more preferably 0.13. If it exceeds the above, it may be difficult to achieve the numerical value in reality.
[0065] The lower limit of the refractive index (ny) in the fast axis direction of the transfer orientation film of the present invention is preferably 1.55, more preferably 1.58, and even more preferably 1.57. The upper limit of the refractive index (ny) in the fast axis direction of the transfer orientation film of the present invention is preferably 1.64, more preferably 1.63, and even more preferably 1.62.
[0066] The lower limit of the refractive index (nx) in the slow axis direction of the transfer orientation film of the present invention is preferably 1.66, more preferably 1.67, and even more preferably 1.68. The upper limit of the refractive index (nx) in the slow axis direction of the transfer orientation film of the present invention is preferably 1.75, more preferably 1.73, even more preferably 1.72, and particularly preferably 1.71.
[0067] The lower limit of the antistatic property (surface resistance) of the transfer orientation film of the present invention is preferably 1×10 5 Ω / □, more preferably 1×10 6 If the resistance is less than the above range, the effect is saturated and no further effect may be obtained. The upper limit of the antistatic property (surface resistance) of the transfer alignment film of the present invention is preferably 1×10 13 Ω / □, more preferably 1×10 12 Ω / □, and more preferably 1×10 11It is Ω / □. If it exceeds the above range, repelling due to static electricity may occur, or the alignment direction of the liquid crystal compound may be disturbed. The antistatic property (surface resistance) can be made within the above range by kneading an antistatic agent into the transfer alignment film, providing an antistatic coating layer under the release layer or on the opposite side, or adding an antistatic agent to the release layer.
[0068] Examples of antistatic agents to be added to the antistatic coating layer, the release layer, or the transfer orientation film include conductive polymers such as polyaniline and polythiophene, ionic polymers such as polystyrene sulfonate, and conductive fine particles such as tin-doped indium oxide and antimony-doped tin oxide.
[0069] The transfer orientation film may be provided with a release layer. However, if the film itself has low adhesion to the transferred material such as the retardation layer or the orientation layer and has sufficient releasability without providing a release layer, the release layer may not be provided. If the adhesion is too low, the adhesion may be adjusted by performing a corona treatment on the surface. The release layer can be formed using a known release agent, and preferred examples include alkyd resins, amino resins, long-chain acrylic acrylates, silicone resins, and fluororesins. These can be appropriately selected according to the adhesion to the transferred material.
[0070] Furthermore, in the alignment film for transfer of the present invention, an easy-adhesion layer may be provided as an underlying layer of the oligomer block coat layer, the antistatic layer, and the release layer.
[0071] (Roughness of release surface) The release surface (A layer surface) of the transfer orientation film of the present invention is preferably smooth.
[0072] The lower limit of the three-dimensional arithmetic mean roughness (SRa) of the release surface of the transfer orientation film of the present invention is preferably 1 nm, more preferably 2 nm. If it is less than the above, it may be difficult to achieve the numerical value in reality. In addition, the upper limit of the SRa of the release surface of the transfer orientation film of the present invention is preferably 30 nm, more preferably 25 nm, even more preferably 20 nm, particularly preferably 15 nm, and most preferably 10 nm.
[0073] The lower limit of the three-dimensional ten-point average roughness (SRz) of the release surface of the transfer orientation film of the present invention is preferably 5 nm, more preferably 10 nm, and even more preferably 13 nm. The upper limit of the SRz of the release surface of the transfer orientation film of the present invention is preferably 200 nm, more preferably 150 nm, even more preferably 120 nm, particularly preferably 100 nm, and most preferably 80 nm.
[0074] The lower limit of the maximum height (SRy: maximum peak height SRp of the release surface + maximum valley depth SRv of the release surface) of the transfer orientation film of the present invention is preferably 10 nm, more preferably 15 nm, and even more preferably 20 nm. The upper limit of SRy of the release surface of the transfer orientation film of the present invention is preferably 300 nm, more preferably 250 nm, even more preferably 150 nm, particularly preferably 120 nm, and most preferably 100 nm.
[0075] The upper limit of the number of protrusions of 0.5 μm or more on the release surface of the orientation film for transfer of the present invention is preferably 5 pieces / m 2 and more preferably 4 pieces / m 2 and more preferably 3 pieces / m 2 and particularly preferably 2 pieces / m 2 and most preferably 1 piece / m 2 It is.
[0076] If the roughness of the release surface exceeds the above range, the alignment state and phase difference may not be as designed in the minute parts of the liquid crystal compound alignment layer formed on the transfer alignment film of the present invention, and defects such as pinholes and scratches may occur. This is thought to be due to the alignment layer peeling off of the convex parts during rubbing, or insufficient rubbing of the foot of the convex parts and the concave parts. In addition, if the release surface layer contains particles, the particles may fall off during rubbing and damage the surface. In addition, whether it is a rubbing alignment layer or a photoalignment layer, when the film is wound up with the alignment layer provided, holes may be made in the alignment layer in the convex parts due to rubbing with the back layer, the alignment may be disturbed by pressure, etc. It is thought that these defects in the alignment layer cause the liquid crystal compound to not be oriented in the minute parts when the liquid crystal compound alignment layer is provided on the alignment layer.
[0077] In the case of a liquid crystal compound alignment layer, it is thought that the designed phase difference cannot be obtained because the thickness of the liquid crystal compound alignment layer becomes thinner at the convex parts and thinner at the concave parts when the liquid crystal compound is applied.
[0078] In order to set the roughness of the release surface (A) within the above range, when the oriented film for transfer of the present invention is a stretched film, the following method can be mentioned. The release side layer (surface layer) of the film roll must not contain particles. If the release side layer (surface layer) of the film roll contains particles, the particles shall be small in size. If the release side layer (surface layer) of the film roll contains particles, a flattening coat should be applied.
[0079] In addition to the above, it is also important to make raw materials and manufacturing processes clean as follows: Filter the particle slurry during polymerization. Filter before chipping. - Clean the cooling water for chip production. Clean the environment for chip transport and feeding into the film-making machine. During film production, the molten resin is filtered to remove agglomerated particles and foreign matter. Filter the coating agent to remove foreign matter. · Film formation, coating and drying are carried out in a clean environment.
[0080] The surface layer is preferably substantially free of particles for smoothing purposes, where substantially free of particles means that the particle content is less than 50 ppm, preferably less than 30 ppm.
[0081] In order to improve the slipperiness of the surface, the surface layer may contain particles. When particles are contained, the lower limit of the surface layer particle content is preferably 0 ppm, more preferably 50 ppm, and even more preferably 100 ppm. The upper limit of the surface layer particle content is preferably 20000 ppm, more preferably 10000 ppm, even more preferably 8000 ppm, and particularly preferably 6000 ppm. If the content exceeds the above, the roughness of the surface layer may not be within the preferred range.
[0082] The lower limit of the surface layer particle diameter is preferably 0.005 μm, more preferably 0.01 μm, and even more preferably 0.02 μm. The upper limit of the surface layer particle diameter is preferably 3 μm, more preferably 1 μm, even more preferably 0.5 μm, and particularly preferably 0.3 μm. If the upper limit exceeds the above range, the roughness of the surface layer may not be within the preferred range.
[0083] Even if the surface layer does not contain particles or has small particles, if the lower layer contains particles, the roughness of the release surface layer may increase due to the influence of the particles in the lower layer. In such cases, it is preferable to increase the thickness of the release surface layer or provide a lower layer (intermediate layer) that does not contain particles.
[0084] The lower limit of the surface layer thickness is preferably 0.1 μm, more preferably 0.5 μm, even more preferably 1 μm, particularly preferably 3 μm, and most preferably 5 μm. The upper limit of the surface layer thickness is preferably 97%, more preferably 95%, and even more preferably 90% of the total thickness of the transfer alignment film.
[0085] The particle-free intermediate layer is essentially free of particles, meaning that the particle content is less than 50 ppm, preferably less than 30 ppm. The lower limit of the thickness of the intermediate layer is preferably 10%, more preferably 20%, and even more preferably 30% of the total thickness of the transfer orientation film. The upper limit is preferably 95%, more preferably 90%.
[0086] When the surface roughness of the transfer orientation film is high, a flattening coat may be provided. Examples of resins used in the flattening coat include polyester, acrylic, polyurethane, polystyrene, polyamide, and other resins that are generally used as coating agent resins. It is also preferable to use crosslinking agents such as melamine, isocyanate, epoxy resin, and oxazoline compounds. These are applied as coating agents dissolved or dispersed in an organic solvent or water and then dried. Alternatively, in the case of acrylic, they may be applied without a solvent and cured by radiation. The flattening coat may be an oligomer block coat. When a release layer is provided by coating, the release layer itself may be thickened.
[0087] The lower limit of the thickness of the surface flattening coating layer is preferably 0.01 μm, more preferably 0.1 μm, even more preferably 0.2 μm, and particularly preferably 0.3 μm. If it is less than the above, the flattening effect may be insufficient. The upper limit of the thickness of the surface flattening coating layer is preferably 10 μm, more preferably 7 μm, even more preferably 5 μm, and particularly preferably 3 μm. If it exceeds the above, further flattening effect may not be obtained.
[0088] The planarizing coat may be applied by in-line coating during the film formation process, or may be applied separately off-line.
[0089] (Roughness of the back side) In addition, even if the release surface of the transfer orientation film of the present invention is smoothed, defects may occur in the liquid crystal compound orientation layer. This is because the transfer orientation film is wound up in a roll shape, and the front and back surfaces are in contact with each other, so the roughness of the back surface is transferred to the front surface (the convex parts of the back surface are transferred to the release layer to form concave parts). In some cases, a masking film is attached to the transfer orientation film provided with a liquid crystal compound orientation layer to protect the liquid crystal compound orientation layer, but it is often wound up as is to reduce costs. When the film is wound up with the orientation layer provided in this way, it is considered that the orientation layer is dented, holes are formed, and the orientation of the orientation layer is disturbed due to the convex parts on the back surface. In addition, after the liquid crystal compound orientation layer is provided, it is considered that the convex parts on the back surface cause holes in the liquid crystal compound orientation layer and the orientation is disturbed. In particular, the pressure is high at the core, and these phenomena are likely to occur. From the above findings, it was found that the above-mentioned defects can be prevented by making the surface (back surface) opposite the release surface have a specific roughness.
[0090] The lower limit of the three-dimensional arithmetic mean roughness (SRa) of the back surface of the transfer orientation film of the present invention is preferably 1 nm, more preferably 2 nm, even more preferably 3 nm, particularly preferably 4 nm, and most preferably 5 nm. The upper limit of the SRa of the back surface of the transfer orientation film of the present invention is preferably 50 nm, more preferably 45 nm, and even more preferably 40 nm. If it exceeds the above range, many defects may occur.
[0091] The lower limit of the three-dimensional ten-point average roughness (SRz) of the back surface of the transfer orientation film of the present invention is preferably 7 nm, more preferably 10 nm, even more preferably 15 nm, particularly preferably 20 nm, and most preferably 25 nm. The upper limit of the SRz of the back surface of the transfer orientation film of the present invention is preferably 1500 nm, more preferably 1200 nm, even more preferably 1000 nm, particularly preferably 700 nm, and most preferably 500 nm. If it exceeds the above, many defects may occur.
[0092] The lower limit of the maximum height of the back surface of the transfer orientation film of the present invention (SRy: maximum back surface peak height SRp + maximum back surface depth SRv) is preferably 15 nm, more preferably 20 nm, even more preferably 25 nm, particularly preferably 30 nm, and most preferably 40 nm. The upper limit of the maximum height SRy of the back surface of the transfer orientation film of the present invention is preferably 2000 nm, more preferably 1500 nm, even more preferably 1200 nm, particularly preferably 1000 nm, and most preferably 700 nm. If it exceeds the above, many defects may occur.
[0093] The upper limit of the number of protrusions having a size of 2 μm or more on the back surface of the orientation film for transfer of the present invention is preferably 5 pieces / m 2 and more preferably 4 pieces / m 2 and more preferably 3 pieces / m 2 and particularly preferably 2 pieces / m 2 and most preferably 1 piece / m 2 If you go beyond that, there may be many drawbacks.
[0094] If the roughness of the back surface of the transfer orientation film of the present invention is less than the above range, the slipperiness of the film will be poor, and the film may become less slippery and more likely to be scratched when transported on a roll or wound up, etc. Also, if the roughness of the back surface of the transfer orientation film of the present invention exceeds the above range, the above-mentioned defects are more likely to occur.
[0095] In order to set the roughness of the back surface within the above range, when the oriented film for transfer of the present invention is a stretched film, the following method can be mentioned. The back layer (back layer) of the film roll is made to contain specific particles. · The film roll is made thinner by using a film containing particles in the middle layer and a film not containing particles on the back layer side (back layer). If the back layer (back layer) of the film roll is very rough, a flattening coat should be applied. If the back layer of the film roll (back layer) does not contain particles or has low roughness, a slippery coating (particle-containing coating) is applied.
[0096] The lower limit of the particle diameter of the back layer is preferably 0.01 μm, more preferably 0.05 μm, and even more preferably 0.1 μm. If it is less than the above, the slipperiness may be poor and winding problems may occur. In addition, the upper limit of the particle diameter of the back layer is preferably 5 μm, more preferably 3 μm, and even more preferably 2 μm. If it exceeds the above, the back surface may become too rough.
[0097] When the back surface contains particles, the content is preferably 50 ppm, more preferably 100 ppm. If the content is less than the above, the effect of slippage caused by adding particles may not be obtained. The upper limit of the particle content in the back surface layer is preferably 10,000 ppm, more preferably 7,000 ppm, and even more preferably 5,000 ppm. If the content exceeds the above, the back surface may become too rough.
[0098] The lower limit of the thickness of the back surface layer is preferably 0.1 μm, more preferably 0.5 μm, even more preferably 1 μm, particularly preferably 3 μm, and most preferably 5 μm. The upper limit of the thickness of the back surface layer is preferably 95%, more preferably 90%, and even more preferably 85% of the total thickness of the transfer alignment film.
[0099] It is also preferable to control the roughness of the back surface by making the intermediate layer contain particles and making the back surface layer thin without containing particles. By adopting such a form, it is possible to ensure the roughness of the back surface while preventing the particles from falling off.
[0100] The particle size and amount of the particles in the intermediate layer are the same as those in the back layer. In this case, the lower limit of the thickness of the back layer is preferably 0.5 μm, more preferably 1 μm, and even more preferably 2 μm. The upper limit of the thickness is preferably 30 μm, more preferably 25 μm, and even more preferably 20 μm.
[0101] When the back surface of the raw film is rough, it is also preferable to provide a flattening coat. The flattening coat may be the same as those mentioned for the front surface.
[0102] The lower limit of the thickness of the back surface flattening coating layer is preferably 0.01 μm, more preferably 0.03 μm, and even more preferably 0.05 μm. If it is less than the above, the flattening effect may be reduced. The upper limit of the thickness of the back surface flattening coating layer is preferably 10 μm, more preferably 5 μm, and even more preferably 3 μm. If it exceeds the above, the flattening effect will be saturated.
[0103] The back side of the raw film may be made free of particles, and a particle-containing easy-slip coating may be provided on the back side. Also, when the roughness of the back side of the raw film is small, a easy-slip coating may be provided.
[0104] The lower limit of the particle size of the backside easy-slip coating layer is preferably 0.01 μm, more preferably 0.05 μm. If it is less than the above, easy slippage may not be obtained. The upper limit of the particle size of the backside easy-slip coating layer is preferably 5 μm, more preferably 3 μm, even more preferably 2 μm, and particularly preferably 1 μm. If it exceeds the above, the roughness of the backside may be too high.
[0105] The lower limit of the particle content of the backside easy-slip coating layer is preferably 0.1% by mass, more preferably 0.5% by mass, even more preferably 1% by mass, particularly preferably 1.5% by mass, and most preferably 2% by mass. If it is less than the above, easy slippage may not be obtained. Also, the upper limit of the particle content of the backside easy-slip coating layer is preferably 20% by mass, more preferably 15% by mass, and even more preferably 10% by mass. If it exceeds the above, the roughness of the backside may be too high.
[0106] The lower limit of the thickness of the backside easy-slip coating layer is preferably 0.01 μm, more preferably 0.03 μm, and even more preferably 0.05 μm. The upper limit of the thickness of the backside easy-slip coating layer is preferably 10 μm, more preferably 5 μm, even more preferably 3 μm, particularly preferably 2 μm, and most preferably 1 μm.
[0107] (Method of manufacturing an orientation film for transfer) Hereinafter, a method for producing an orientation film for transfer of the present invention in the case where the orientation film for transfer is a stretched film will be described. When MD stretching is performed, the lower limit of the MD magnification is preferably 1.5 times. The upper limit is preferably 6 times, more preferably 5.5 times, and even more preferably 5 times. When TD stretching is performed, the lower limit of the TD magnification is preferably 1.5 times. The upper limit of the TD magnification is preferably 6 times, more preferably 5.5 times, and even more preferably 5 times.
[0108] The lower limit of the HS temperature is preferably 150° C., more preferably 170° C. If it is less than the above, the heat shrinkage rate may not decrease. The upper limit of the HS temperature is preferably 240° C., more preferably 230° C. If it exceeds the above, the resin may deteriorate.
[0109] The lower limit of the TD relaxation rate is preferably 0.1%, more preferably 0.5%. If it is less than the above, the heat shrinkage rate may not decrease. The upper limit of the TD relaxation rate is preferably 8%, more preferably 6%, and even more preferably 5%. If it exceeds the above, sagging may cause poor flatness or uneven thickness.
[0110] The annealing treatment is preferably carried out by unwinding the film, passing it through an oven and then winding it up.
[0111] The lower limit of the annealing temperature is preferably 80° C., more preferably 90° C., and even more preferably 100° C. If the temperature is lower than the above, the annealing effect may not be obtained. The upper limit of the annealing temperature is preferably 200° C., more preferably 180° C., and even more preferably 160° C. If the temperature exceeds the above, the flatness may decrease and the heat shrinkage may increase.
[0112] The lower limit of the annealing time is preferably 5 seconds, more preferably 10 seconds, and even more preferably 15 seconds. If it is less than the above, the annealing effect may not be obtained. The upper limit of the annealing time is preferably 10 minutes, more preferably 5 minutes, even more preferably 3 minutes, and particularly preferably 1 minute. If it exceeds the above, not only the effect becomes saturated, but also a large oven may be required, and productivity may be deteriorated.
[0113] In the annealing treatment, the relaxation rate can be adjusted by adjusting the difference in peripheral speed between the unwinding speed and the winding speed, or by adjusting the winding tension. The lower limit of the relaxation rate is preferably 0.5%. If it is less than this, the annealing effect may not be obtained. The upper limit of the relaxation rate is preferably 8%, more preferably 6%, and even more preferably 5%. If it exceeds the above, the flatness may decrease or winding problems may occur.
[0114] (Laminate for transferring liquid crystal compound alignment layer) Next, the laminate for transferring a liquid crystal compound alignment layer of the present invention will be described. The laminate for transferring a liquid crystal compound alignment layer of the present invention has a structure in which a liquid crystal compound alignment layer and the alignment film for transfer of the present invention are laminated. The liquid crystal compound alignment layer needs to be coated on the alignment film for transfer and aligned. As an alignment method, there is a method of providing an alignment control function by subjecting the lower layer (release surface) of the liquid crystal compound alignment layer to a rubbing treatment or the like, and a method of directly aligning the liquid crystal compound by irradiating it with polarized ultraviolet light or the like after coating the liquid crystal compound.
[0115] (Orientation control layer) Also, a method of providing an orientation control layer on the transfer orientation film and providing a liquid crystal compound orientation layer on the orientation control layer is also preferred. In the present invention, the liquid crystal compound orientation layer may be a collective term for the orientation control layer and the liquid crystal compound orientation layer, rather than the liquid crystal compound orientation layer alone. As the orientation control layer, any orientation control layer may be used as long as it can bring the liquid crystal compound orientation layer into a desired orientation state. Suitable examples of the orientation control layer include a rubbing treatment orientation control layer obtained by rubbing a resin coating film, and a photo-orientation control layer that aligns molecules by irradiating polarized light to generate an orientation function.
[0116] (Rubbing treatment alignment control layer) As the polymer material used for the alignment control layer formed by rubbing treatment, polyvinyl alcohol and its derivatives, polyimide and its derivatives, acrylic resin, polysiloxane derivatives, etc. are preferably used.
[0117] The method for forming the rubbing treatment alignment control layer will be described below. First, the rubbing treatment alignment control layer coating liquid containing the above polymer material is applied onto the release surface of the alignment film, and then heated and dried to obtain the alignment control layer before rubbing treatment. The alignment control layer coating liquid may contain a crosslinking agent.
[0118] The solvent of the rubbing treatment alignment control layer coating solution can be used without any limitation as long as it dissolves the polymer material. Specific examples include alcohols such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, and cellosolve; ester-based solvents such as ethyl acetate, butyl acetate, and gamma-butyrolactone; ketone-based solvents such as acetone, methyl ethyl ketone, cyclopentanone, and cyclohexanone; aromatic hydrocarbon solvents such as toluene and xylene; and ether-based solvents such as tetrahydrofuran and dimethoxyethane. These solvents may be used alone or in combination.
[0119] The concentration of the coating solution for the rubbing treatment alignment control layer can be appropriately adjusted depending on the type of polymer and the thickness of the alignment control layer to be produced, but is preferably 0.2 to 20 mass %, particularly preferably 0.3 to 10 mass %, in terms of solid content concentration. As the coating method, a known method such as a coating method such as a gravure coating method, a die coating method, a bar coating method, or an applicator method, or a printing method such as a flexographic method can be used.
[0120] The heating and drying temperature depends on the transfer orientation film, but in the case of PET, it is preferably in the range of 30°C to 170°C, more preferably 50 to 150°C, and even more preferably 70 to 130°C. If the drying temperature is low, it becomes necessary to take a long drying time, which may result in poor productivity. If the drying temperature is too high, the transfer orientation film may stretch due to heat or may become significantly thermally contracted, making it impossible to achieve the designed optical function, or may result in poor flatness. The heating and drying time may be, for example, 0.5 to 30 minutes, more preferably 1 to 20 minutes, and even more preferably 2 to 10 minutes.
[0121] The thickness of the rubbing treatment alignment control layer is preferably 0.01 to 10 μm, more preferably 0.05 to 5 μm, and particularly preferably 0.1 to 1 μm.
[0122] Next, a rubbing treatment is performed. The rubbing treatment can generally be performed by rubbing the surface of the polymer layer with paper or cloth in a certain direction. In general, the surface of the alignment control layer is rubbed using a rubbing roller made of a raised cloth of fibers such as nylon, polyester, or acrylic. In order to provide a liquid crystal compound alignment control layer that is aligned in a specific direction oblique to the longitudinal direction of a long film, the rubbing direction of the alignment control layer must be set at a corresponding angle. The angle can be adjusted by adjusting the angle between the rubbing roller and the alignment film, and by adjusting the conveying speed of the alignment film and the rotation speed of the roller.
[0123] It is also possible to directly subject the release surface of the transfer alignment film to a rubbing treatment so as to provide the surface of the transfer alignment film with an alignment control function, and this case is also within the technical scope of the present invention.
[0124] (Photo alignment control layer) The photo-alignment control layer is an alignment film to which an alignment control force is imparted by applying a coating liquid containing a polymer or monomer having a photoreactive group and a solvent to an alignment film and irradiating the film with polarized light, preferably polarized ultraviolet light. The photoreactive group is a group that generates a liquid crystal alignment ability by light irradiation. Specifically, it is a group that generates a photoreaction that is the origin of the liquid crystal alignment ability, such as molecular orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, which occurs by light irradiation. Among the photoreactive groups, those that cause a dimerization reaction or a photocrosslinking reaction are preferred in terms of excellent alignment and maintaining the smectic liquid crystal state of the liquid crystal compound alignment layer. As the photoreactive group that can cause the above-mentioned reaction, an unsaturated bond, particularly a double bond, is preferable, and a group having at least one selected from the group consisting of a C=C bond, a C=N bond, an N=N bond, and a C=O bond is particularly preferable.
[0125] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazolyl groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, and formazan groups, as well as groups having an azoxybenzene as a basic structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.
[0126] Among them, photoreactive groups capable of photodimerization are preferred, and cinnamoyl and chalcone groups are preferred because the amount of polarized light irradiation required for photoalignment is relatively small, and a photoalignment layer having excellent thermal stability and stability over time is easily obtained. Furthermore, as a polymer having a photoreactive group, a polymer having a cinnamoyl group at the end of the polymer side chain that has a cinnamic acid structure is particularly preferred. Examples of the main chain structure include polyimide, polyamide, (meth)acrylic, and polyester.
[0127] Specific examples of the orientation control layer include those described in JP-A-2006-285197, JP-A-2007-76839, JP-A-2007-138138, JP-A-2007-94071, JP-A-2007-121721, JP-A-2007-140465, JP-A-2007-156439, JP-A-2007-133184, and JP-A-2009 Examples of the orientation control layers include those described in JP-A-109831, JP-A-2002-229039, JP-A-2002-265541, JP-A-2002-317013, JP-T-2003-520878, JP-T-2004-529220, JP-A-2013-33248, JP-A-2015-7702, and JP-A-2015-129210.
[0128] The solvent for the coating liquid for forming the photo-alignment control layer can be used without any limitation as long as it dissolves the polymer and monomer having a photoreactive group. Specific examples include those mentioned in the method for forming the alignment control layer by rubbing treatment. It is also preferable to add a photopolymerization initiator, a polymerization inhibitor, and various stabilizers to the coating liquid for forming the photo-alignment control layer. In addition, a polymer other than the polymer and monomer having a photoreactive group, or a monomer not having a photoreactive group that is copolymerizable with the monomer having a photoreactive group may be added.
[0129] The concentration, coating method, and drying conditions of the coating solution for forming the photo-alignment control layer can be exemplified by those mentioned in the method for forming the rubbing treatment alignment control layer. The preferred thickness is also the same as that of the rubbing treatment alignment control layer.
[0130] The polarized light is preferably irradiated from the direction of the surface of the photo-alignment control layer before alignment. When the alignment direction of the photo-alignment control layer is parallel or perpendicular to the alignment direction of the alignment film for transfer, the polarized light may be irradiated through the alignment film for transfer.
[0131] The wavelength of the polarized light is preferably in a wavelength range where the photoreactive group of the polymer or monomer having the photoreactive group can absorb light energy. Specifically, ultraviolet light having a wavelength of 250 to 400 nm is preferable. Examples of the light source of the polarized light include a xenon lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, and an ultraviolet laser such as KrF or ArF, and the high-pressure mercury lamp, the ultra-high-pressure mercury lamp, and the metal halide lamp are preferable.
[0132] Polarized light can be obtained, for example, by passing the light from the light source through a polarizer. The direction of polarization can be adjusted by adjusting the polarization angle of the polarizer. Examples of the polarizer include a polarizing filter, a polarizing prism such as a Glan-Thompson or Glan-Taylor type, and a wire grid type polarizer. It is preferable that the polarized light is substantially parallel light.
[0133] By adjusting the angle of the irradiated polarized light, the direction of the alignment regulating force of the photoalignment layer can be adjusted as desired.
[0134] The irradiation intensity varies depending on the type and amount of polymerization initiator and resin (monomer), but for example, it is 10 to 10,000 mJ / cm at 365 nm. 2 is preferable, and more preferably 20 to 5000 mJ / cm 2 is preferred.
[0135] (Liquid crystal compound alignment layer) The liquid crystal compound alignment layer is not particularly limited as long as the liquid crystal compound is aligned. Specific examples include a polarizing film (polarizer) containing a liquid crystal compound and a dichroic dye, and a retardation layer containing a rod-shaped or discotic liquid crystal compound.
[0136] (Polarizing film) The polarizing film has a function of transmitting polarized light in only one direction, and contains a dichroic dye.
[0137] (dichroic dye) A dichroic dye is a dye that has different absorbance in the long axis direction of the molecule and absorbance in the short axis direction.
[0138] The dichroic dye preferably has a maximum absorption wavelength (λMAX) in the range of 300 to 700 nm. Examples of such dichroic dyes include acridine dyes, oxazine dyes, cyanine dyes, naphthalene dyes, azo dyes, and anthraquinone dyes, and among these, azo dyes are preferred. Examples of azo dyes include monoazo dyes, bisazo dyes, trisazo dyes, tetrakisazo dyes, and stilbene azo dyes, and preferably bisazo dyes and trisazo dyes. The dichroic dyes may be used alone or in combination, but it is preferable to combine two or more types in order to adjust the color tone (achromatic color). In particular, it is preferable to combine three or more types. In particular, it is preferable to combine three or more types of azo compounds.
[0139] Preferred azo compounds include dyes described in JP-A-2007-126628, JP-A-2010-168570, JP-A-2013-101328, and JP-A-2013-210624.
[0140] The dichroic dye is preferably a dichroic dye polymer introduced into the side chain of a polymer such as an acrylic polymer. Examples of such dichroic dye polymers include the polymers described in JP-A-2016-4055 and polymers obtained by polymerizing the compounds of [Chemical formula 6] to [Chemical formula 12] in JP-A-2014-206682.
[0141] From the viewpoint of obtaining good alignment of the dichroic dye, the content of the dichroic dye in the polarizing film is preferably from 0.1 to 30% by mass, more preferably from 0.5 to 20% by mass, further preferably from 1.0 to 15% by mass, and particularly preferably from 2.0 to 10% by mass.
[0142] The polarizing film preferably further contains a polymerizable liquid crystal compound in order to improve the film strength, polarization degree, and film uniformity. The polymerizable liquid crystal compound here also includes a polymerized film.
[0143] (Polymerizable liquid crystal compound) The polymerizable liquid crystal compound is a compound that has a polymerizable group and exhibits liquid crystallinity. The polymerizable group means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. Here, the photopolymerizable group means a group that can undergo a polymerization reaction by an active radical or an acid generated from a photopolymerization initiator described later. Examples of the polymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred. The compound exhibiting liquid crystallinity may be a thermotropic liquid crystal or a lyotropic liquid crystal, and may be a nematic liquid crystal or a smectic liquid crystal in a thermotropic liquid crystal.
[0144] The polymerizable liquid crystal compound is preferably a smectic liquid crystal compound, and more preferably a high-order smectic liquid crystal compound, in that higher polarization properties can be obtained. When the liquid crystal phase formed by the polymerizable liquid crystal compound is a high-order smectic phase, a polarizing film with a higher degree of orientation order can be produced.
[0145] Specific preferred polymerizable liquid crystal compounds include those described in, for example, JP-A-2002-308832, JP-A-2007-16207, JP-A-2015-163596, JP-T-2007-510946, JP-T-2013-114131, WO2005 / 045485, Lub et al. Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996), and the like.
[0146] From the viewpoint of increasing the alignment property of the polymerizable liquid crystal compound, the content of the polymerizable liquid crystal compound in the polarizing film is preferably 70 to 99.5% by mass, more preferably 75 to 99% by mass, even more preferably 80 to 97% by mass, and particularly preferably 83 to 95% by mass.
[0147] The polarizing film can be provided by applying a polarizing film composition coating. The polarizing film composition coating may contain a solvent, a polymerization initiator, a sensitizer, a polymerization inhibitor, a leveling agent, a polymerizable non-liquid crystal compound, a crosslinking agent, and the like.
[0148] As the solvent, those exemplified as the solvent for the alignment layer coating liquid are preferably used.
[0149] The polymerization initiator is not limited as long as it polymerizes the polymerizable liquid crystal compound, but a photopolymerization initiator that generates active radicals by light is preferable. Examples of the polymerization initiator include benzoin compounds, benzophenone compounds, alkylphenone compounds, acylphosphine oxide compounds, triazine compounds, iodonium salts, and sulfonium salts.
[0150] The sensitizer is preferably a photosensitizer, examples of which include a xanthone compound, an anthracene compound, phenothiazine, and rubrene.
[0151] Examples of the polymerization inhibitor include hydroquinones, catechols, and thiophenols.
[0152] The polymerizable non-liquid crystal compound is preferably one that copolymerizes with the polymerizable liquid crystal compound, and for example, when the polymerizable liquid crystal compound has a (meth)acryloyloxy group, (meth)acrylates can be mentioned. The (meth)acrylates may be monofunctional or polyfunctional. By using polyfunctional (meth)acrylates, the strength of the polarizing film can be improved. When a polymerizable non-liquid crystal compound is used, it is preferably 1 to 15% by mass in the polarizing film, more preferably 2 to 10% by mass, and particularly preferably 3 to 7% by mass. If it exceeds 15% by mass, the degree of polarization may decrease.
[0153] Examples of the crosslinking agent include compounds capable of reacting with functional groups of the polymerizable liquid crystal compound and the polymerizable non-liquid crystal compound, such as isocyanate compounds, melamine, epoxy resins, and oxazoline compounds.
[0154] The polarizing film composition coating is applied directly onto an orientation film for transfer or onto an orientation control layer, and then dried, heated and cured as necessary to provide a polarizing film.
[0155] As a coating method, a known method such as a gravure coating method, a die coating method, a bar coating method, an applicator method, or a printing method such as a flexography method can be used.
[0156] The coated orientation film for transfer is guided to a hot air dryer, an infrared dryer or the like and dried at 30 to 170° C., more preferably 50 to 150° C., and even more preferably 70 to 130° C. The drying time is preferably 0.5 to 30 minutes, more preferably 1 to 20 minutes, and even more preferably 2 to 10 minutes.
[0157] Heating can be performed in order to more firmly align the dichroic dye and the polymerizable liquid crystal compound in the polarizing film. The heating temperature is preferably set within a temperature range in which the polymerizable liquid crystal compound forms a liquid crystal phase.
[0158] When the polarizing film composition coating contains a polymerizable liquid crystal compound, it is preferable to cure it. Examples of the curing method include heating and light irradiation, and light irradiation is preferable. The dichroic dye can be fixed in an oriented state by curing. Curing is preferably performed in a state in which a liquid crystal phase is formed in the polymerizable liquid crystal compound, and curing may be performed by irradiating with light at a temperature at which the compound shows a liquid crystal phase. Examples of light used in the light irradiation include visible light, ultraviolet light, and laser light. In terms of ease of handling, ultraviolet light is preferable.
[0159] The irradiation intensity varies depending on the type and amount of polymerization initiator and resin (monomer), but for example, it is 100 to 10,000 mJ / cm at 365 nm. 2is preferable, and more preferably 200 to 5000 mJ / cm 2 is preferred.
[0160] A polarizing film is formed by applying a polarizing film composition coating onto an orientation control layer, so that the dye is aligned along the orientation direction of the orientation layer, resulting in a polarized light transmission axis in a predetermined direction. However, when the composition is directly applied to an orientation film for transfer without providing an orientation control layer, the polarizing film can also be aligned by irradiating the composition for forming the polarizing film with polarized light to harden it. In this case, polarized light in a desired direction (for example, polarized light in an oblique direction) is irradiated to the longitudinal direction of the orientation film for transfer. It is preferable to further align the dichroic dye firmly along the orientation direction of the polymer liquid crystal by heat treatment thereafter.
[0161] The thickness of the polarizing film is from 0.1 to 5 μm, preferably from 0.3 to 3 μm, and more preferably from 0.5 to 2 μm.
[0162] (phase contrast layer) Representative examples of retardation layers include those provided between the polarizer and liquid crystal cell of a liquid crystal display device for optical compensation, and λ / 4 and λ / 2 layers of a circular polarizer, etc. As liquid crystal compounds, rod-shaped liquid crystal compounds, discotic liquid crystal compounds, etc., such as positive and negative A plates, positive and negative C plates, and O plates, can be used according to the purpose.
[0163] When used as optical compensation for a liquid crystal display device, the degree of retardation is appropriately set according to the type of liquid crystal cell and the properties of the liquid crystal compound used in the cell. For example, in the case of the TN mode, an O plate using a discotic liquid crystal is preferably used. In the case of the VA mode or the IPS mode, a C plate or an A plate using a rod-shaped liquid crystal compound or a discotic liquid crystal compound is preferably used. In addition, in the case of the λ / 4 retardation layer or the λ / 2 retardation layer of a circular polarizer, it is preferable to use an A plate using a rod-shaped compound. These retardation layers may be used not only as a single layer, but also as a combination of multiple layers.
[0164] The liquid crystal compound used in these retardation layers is preferably a polymerizable liquid crystal compound having a polymerizable group such as a double bond, in terms of being able to fix the alignment state.
[0165] Examples of the rod-shaped liquid crystal compound include rod-shaped liquid crystal compounds having a polymerizable group described in JP-A-2002-030042, JP-A-2004-204190, JP-A-2005-263789, JP-A-2007-119415, JP-A-2007-186430, and JP-A-11-513360. Specific compounds include: CH2=CHCOO-(CH2)mO-Ph1-COO-Ph2-OCO-Ph1-O-(CH2)n-OCO-CH=CH2 CH2=CHCOO-(CH2)mO-Ph1-COO-NPh-OCO-Ph1-O-(CH2)n-OCO-CH=CH2 CH2=CHCOO-(CH2)mO-Ph1-COO-Ph2-OCH3 CH2=CHCOO-(CH2)mO-Ph1-COO-Ph1-Ph1-CH2CH(CH3)C2H5 In the formula, m and n are integers of 2 to 6. Ph1 and Ph2 are 1,4-phenyl groups (Ph2 may have a methyl group at the 2-position), NPh is the 2,6-naphthyl group Examples include: These rod-shaped liquid crystal compounds are commercially available as LC242 manufactured by BASF, and these compounds can be used.
[0166] These rod-shaped liquid crystal compounds may be used in combination of two or more kinds in any ratio.
[0167] Examples of discotic liquid crystal compounds include benzene derivatives, truxene derivatives, cyclohexane derivatives, azacrowns, and phenylacetylene macrocycles. Various compounds are described in JP-A-2001-155866, and these compounds are preferably used. Among them, as the discotic compound, a compound having a triphenylene ring represented by the following general formula (1) is preferably used. In the formula, R1 to R6 are each independently hydrogen, halogen, an alkyl group, or a group represented by -OX (wherein X is an alkyl group, an acyl group, an alkoxybenzyl group, an epoxy-modified alkoxybenzyl group, an acryloyloxy-modified alkoxybenzyl group, or an acryloyloxy-modified alkyl group). R1 to R6 are preferably an acryloyloxy-modified alkoxybenzyl group represented by the following general formula (2) (wherein m is 4 to 10). JPEG2024170606000002.jpg53162
[0168] The retardation layer can be provided by applying a composition coating material for the retardation layer. The composition coating material for the retardation layer may contain a solvent, a polymerization initiator, a sensitizer, a polymerization inhibitor, a leveling agent, a polymerizable non-liquid crystal compound, a crosslinking agent, etc. These can be the same as those described in the alignment control layer and the liquid crystal polarizer.
[0169] The retardation layer is provided by applying the retardation layer composition coating material onto the release surface of the alignment film or onto the alignment control layer, followed by drying, heating and curing.
[0170] Among these conditions, the conditions explained in the section on the alignment control layer and the liquid crystal polarizer are preferably used.
[0171] A plurality of retardation layers may be provided. In this case, a plurality of retardation layers may be provided on a single transfer orientation film and then transferred to the target object, or a plurality of types of films each having a single retardation layer provided on a single transfer orientation film may be prepared and then transferred to the target object in sequence.
[0172] The polarizing layer and the retardation layer may be provided on one transfer orientation film, which may then be transferred to the target. In addition, a protective layer may be provided between the polarizer and the retardation layer, or on or between the retardation layers. These protective layers may also be provided on the transfer orientation film together with the retardation layer and the polarizing layer, and then transferred to the target.
[0173] The protective layer may be a coating layer of a transparent resin. The transparent resin may be, but is not limited to, polyvinyl alcohol, ethylene vinyl alcohol copolymer, polyester, polyurethane, polyamide, polystyrene, acrylic resin, epoxy resin, etc. A crosslinking agent may be added to these resins to form a crosslinked structure. A hard coat may also be a cured photocurable composition such as acrylic. After providing a protective layer on an alignment film, the protective layer may be subjected to a rubbing treatment, and a liquid crystal compound alignment layer may be provided thereon without providing an alignment layer.
[0174] (Method of manufacturing a liquid crystal compound alignment layer laminated polarizing plate) Next, a method for producing the liquid crystal compound alignment layer laminated polarizing plate of the present invention will be described. The method for producing a liquid crystal compound alignment layer laminated polarizing plate of the present invention includes a step of bonding a polarizing plate and a liquid crystal compound alignment layer surface of the liquid crystal compound alignment layer transfer laminate of the present invention to form an intermediate laminate, and a step of peeling off the alignment film from the intermediate laminate. Hereinafter, the liquid crystal compound alignment layer will be described as an example when it is used in a circular polarizing plate. In the case of a circular polarizing plate, a λ / 4 layer is used as a retardation layer (referred to as a liquid crystal compound alignment layer in a transfer laminate). The front retardation of the λ / 4 layer is preferably 100 to 180 nm. More preferably, it is 120 to 150 nm. When only a λ / 4 layer is used as a circular polarizing plate, the alignment axis (slow axis) of the λ / 4 layer and the transmission axis of the polarizer are preferably 35 to 55 degrees, more preferably 40 to 50 degrees, and even more preferably 42 to 48 degrees. When used in combination with a polarizer of a stretched film of polyvinyl alcohol, the absorption axis of the polarizer is generally in the length direction of the long polarizing film, so when a λ / 4 layer is provided on a long transfer orientation film, it is preferable to align the liquid crystal compound so that it is in the above range with respect to the length direction of the long transfer orientation film. Note that, when the angle of the transmission axis of the polarizer is different from the above, the liquid crystal compound is oriented so that the above relationship is satisfied by taking into account the angle of the transmission axis of the polarizer.
[0175] A circular polarizing plate is produced by transferring the λ / 4 layer in the transfer laminate in which the λ / 4 layer and the alignment film are laminated to a polarizing plate. Specifically, the polarizing plate and the λ / 4 layer surface of the transfer laminate are bonded to form an intermediate laminate, and the alignment film is peeled off from this intermediate laminate. The polarizing plate may have a protective film on both sides of the polarizer, but it is preferable that the protective film is provided only on one side. If the polarizing plate has a protective film provided only on one side, it is preferable to bond a retardation layer to the opposite side (polarizer surface) of the protective film. If protective films are provided on both sides, it is preferable to bond the retardation layer to the surface intended for the image cell side. The surface intended for the image cell side is a surface that is not surface-treated and is generally provided on the viewing side, such as a low reflection layer, an anti-reflection layer, or an anti-glare layer. The protective film on the side to which the retardation layer is bonded is preferably a protective film with no retardation, such as TAC, acrylic, or COP.
[0176] Examples of polarizers include polarizers prepared by stretching a PVA-based film alone, polarizers prepared by coating an unstretched substrate such as polyester or polypropylene with PVA and stretching the substrate together to prepare a polarizer, which is then transferred to a polarizer protective film, and polarizers composed of a liquid crystal compound and a dichroic dye that are coated or transferred to a polarizer protective film. Any of these polarizers are preferably used.
[0177] As a method for attaching, a conventional adhesive or pressure-sensitive adhesive can be used. As an adhesive, a polyvinyl alcohol adhesive, an ultraviolet-curing adhesive such as acrylic or epoxy, or a heat-curing adhesive such as epoxy or isocyanate (urethane) is preferably used. As an adhesive, an acrylic, urethane, or rubber-based adhesive can be used. It is also preferable to use an optically transparent pressure-sensitive adhesive sheet without an acrylic substrate.
[0178] When a transfer type polarizer is used, the polarizer may be transferred onto the retardation layer (liquid crystal compound alignment layer) of the transfer laminate, and then the polarizer and the retardation layer may be transferred onto the target object (polarizer protective film).
[0179] The polarizer protective film on the opposite side to the side where the retardation layer is provided can be made of generally known materials such as TAC, acrylic, COP, polycarbonate, polyester, etc. Among these, TAC, acrylic, COP, and polyester are preferred. Polyester is preferably polyethylene terephthalate. In the case of polyester, it is preferred that the film is a zero retardation film with an in-plane retardation of 100 nm or less, particularly 50 nm or less, or a high retardation film of 3000 nm to 30000 nm.
[0180] When a high retardation film is used, in order to prevent blackout or coloring when viewing an image through polarized sunglasses, the angle between the transmission axis of the polarizer and the slow axis of the high retardation film is preferably in the range of 30 to 60 degrees, more preferably in the range of 35 to 55 degrees. In order to reduce rainbow spots when observed from a shallow oblique angle with the naked eye, the angle between the transmission axis of the polarizer and the slow axis of the high retardation film is preferably 10 degrees or less, more preferably 7 degrees or less, or 80 to 100 degrees, more preferably 83 to 97 degrees.
[0181] The polarizer protective film on the opposite side may be provided with an antiglare layer, an antireflection layer, a low reflection layer, a hard coat layer, or the like.
[0182] (Composite retardation layer) When the λ / 4 layer is used alone, it may not be λ / 4 over a wide range of the visible light region, and coloring may occur. Therefore, the λ / 4 layer may be used in combination with the λ / 2 layer. The front retardation of the λ / 2 layer is preferably 200 to 360 nm, and more preferably 240 to 300 nm.
[0183] In this case, it is preferable that the λ / 4 layer and the λ / 2 layer are arranged at an angle such that the sum of the layers is λ / 4. Specifically, the angle (θ) between the alignment axis (slow axis) of the λ / 2 layer and the transmission axis of the polarizer is preferably 5 to 20 degrees, more preferably 7 to 17 degrees. The angle between the alignment axis (slow axis) of the λ / 2 layer and the alignment axis (slow axis) of the λ / 4 layer is preferably in the range of 2θ+45 degrees±10 degrees, more preferably in the range of 2θ+45 degrees±5 degrees, and even more preferably in the range of 2θ+45 degrees±3 degrees.
[0184] In this case, when used in combination with a polarizer made of a stretched polyvinyl alcohol film, the absorption axis of the polarizer is generally in the length direction of the long polarizer film, so when a λ / 2 layer or λ / 4 layer is provided on a long oriented film for transfer, it is preferable to align the liquid crystal compound so that the above range is satisfied with respect to the length direction or the direction perpendicular to the length of the long oriented film for transfer. If the angle of the transmission axis of the polarizer is different from the above, the liquid crystal compound is oriented so that the above relationship is satisfied, taking into account the angle of the transmission axis of the polarizer.
[0185] As examples of these methods and retardation layers, reference can be made to JP-A-2008-149577, JP-A-2002-303722, WO2006 / 100830, JP-A-2015-64418, and the like.
[0186] Furthermore, it is also a preferred embodiment to provide a C-plate layer on the λ / 4 layer to reduce changes in color when viewed from an oblique angle. A positive or negative C-plate layer is used depending on the characteristics of the λ / 4 or λ / 2 layer.
[0187] As a lamination method for these, for example, in the case of a combination of a λ / 4 layer and a λ / 2 layer, A λ / 2 layer is formed on the polarizer by transfer printing, and a λ / 4 layer is further formed on top of that by transfer printing. A λ / 4 layer and a λ / 2 layer are provided in this order on an orientation film for transfer, and then transferred onto a polarizer. · A λ / 4 layer, a λ / 2 layer, and a polarizing layer are placed in that order on the transfer orientation film, and then this is transferred to the target object. · A λ / 2 layer and a polarizing layer are placed in that order on the transfer orientation film, this is transferred to the target object, and a λ / 4 layer is then transferred on top of this. Various methods can be adopted.
[0188] Also, when laminating a C plate, various methods can be used, such as a method of transferring a C plate layer onto a λ / 4 layer provided on a polarizer, or a method of providing a C plate layer on an alignment film, and then providing a λ / 4 layer or a λ / 2 layer and a λ / 4 layer on top of the C plate, and then transferring the C plate layer.
[0189] The thickness of the circularly polarizing plate thus obtained is preferably 120 μm or less, more preferably 100 μm or less, further preferably 90 μm or less, particularly preferably 80 μm or less, and most preferably 70 μm or less.
[0190] (Method of inspecting laminate for transferring liquid crystal compound alignment layer) Next, a method for inspecting the laminate for transferring a liquid crystal compound alignment layer of the present invention will be described. The method for inspecting the laminate for transferring the alignment layer of a liquid crystal compound of the present invention includes the steps of irradiating the alignment film surface of the laminate with linearly polarized light having an electric field vibration direction parallel to the alignment direction of the alignment film, or a direction perpendicular to the alignment direction, or a flow direction of the alignment film, or a direction perpendicular to the flow direction, receiving the light on the liquid crystal compound alignment layer surface side, and inspecting whether or not the received light is in an extinction state. Thus, in the present invention, the laminate for transferring the alignment layer of a liquid crystal compound can be inspected for its optical properties in a state where it is laminated on the alignment film for transfer, even if the alignment layer of the liquid crystal compound is a retardation layer.
[0191] In order to inspect the optical state of the retardation layer, linearly polarized light parallel or perpendicular to the orientation direction of the transfer orientation film is irradiated, and the change in the polarization state is detected by a photodetector installed on the opposite side of the laminate. Parallel to the orientation direction of the transfer orientation film is preferably -10 to +10 degrees, more preferably -7 to 7 degrees, even more preferably -5 to 5 degrees, particularly preferably -3 to 3 degrees, and most preferably -2 to 2 degrees. Perpendicular to the orientation direction of the transfer orientation film is preferably 80 to 100 degrees, more preferably 83 to 97 degrees, even more preferably 85 to 95 degrees, particularly preferably 87 to 93 degrees, and most preferably 88 to 92 degrees. If the above range is exceeded, the polarized light that hits the retardation layer or the polarized light that has passed through it may be disturbed by the influence of the phase difference of the substrate, making it impossible to perform accurate evaluation.
[0192] Although the angle of the linearly polarized light to be irradiated may be adjusted according to the orientation direction of the transfer orientation film, the inspection becomes complicated. Therefore, it is also preferable to fix the linearly polarized light to be irradiated as parallel or perpendicular to the flow direction of the transfer orientation film for inspection. Here, the range of parallel or perpendicular is the same as above.
[0193] It is preferable to provide a polarizing filter between the light receiver and the laminate for transferring the liquid crystal compound alignment layer (retardation layer) (film to be inspected). In addition, it is preferable to provide a retardation plate between the laminate for transferring the liquid crystal compound alignment layer (retardation layer) and the polarizing filter to convert the light that has become elliptically polarized by the retardation layer of the laminate for transferring the liquid crystal compound alignment layer (retardation layer) into linearly polarized light if the light is elliptically polarized as designed. For example, by using such a configuration, if the retardation layer is as designed, the light detected by the light receiver is in an extinction state, but if there is light leakage, it is found that the retardation layer is deviated from the design. It is also possible to install multiple types of light receivers with slightly different angles of the polarizing filter and angles and retardation of the retardation plate to detect in which direction and how much the retardation and orientation direction of the retardation layer are deviated.
[0194] (Polarizing layer inspection) When the liquid crystal compound alignment layer is a polarizing layer, the polarizing layer can be inspected by irradiating it with natural light (non-polarized light) and receiving the transmitted light through a polarizing filter. It can also be inspected by irradiating the laminate for transfer with linearly polarized light through a polarizing filter and receiving the transmitted light. In these cases, the polarizing filter is set to an angle at which the polarizing layer provided on the alignment film for transfer is extinguished when it is as designed.
[0195] In addition, by installing multiple types of photodetectors with slightly different angles of polarizing filters, it is possible to detect in which direction and by how much the orientation direction has shifted.
[0196] In these cases, it is preferable to irradiate the film with natural light from the surface of the alignment film for transfer, and to irradiate the film with linearly polarized light from the surface of the polarizing layer. EXAMPLES
[0197] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples, and can be practiced with appropriate modifications within the scope of the present invention, all of which are included in the technical scope of the present invention. The methods for evaluating physical properties in the examples are as follows.
[0198] (1) The angle between the orientation direction of the transfer orientation film and the flow direction or the direction perpendicular to the flow direction of the orientation film, and the difference in the orientation angle in the width direction of the film First, the film was pulled out from the roll, and the orientation direction was determined at five points: both ends (5 cm inward from each end), the center, and the middle part between the center and both ends. The middle part between the center and both ends is located at a position that divides the distance between the center and both ends in half. The orientation direction was determined as the slow axis direction of the film determined using a molecular orientation meter (MOA-6004 type molecular orientation meter, manufactured by Oji Measurement Instruments Co., Ltd.). Next, it was examined whether the overall orientation direction of the film was close to the machine direction (MD) or the transverse direction (TD). When the overall orientation direction of the film was close to the machine direction, the angle between the orientation direction and the machine direction of the film was determined at each of the above five points, and the value at the point with the largest angle was adopted as the maximum value of the "angle between the orientation direction of the oriented film and the machine direction of the oriented film." On the other hand, when the overall orientation direction of the film was close to the width direction, the angle between the orientation direction and the direction perpendicular to the film flow direction was determined at each of the above five locations, and the value at the location where the angle was the largest was adopted as the maximum value of the "angle between the orientation direction of the oriented film and the direction perpendicular to the film flow direction." Moreover, the difference between the maximum and minimum angles among the angles determined at the above five locations was defined as the "angle difference of the orientation angle in the width direction of the film." The angle is considered to be a positive value when the orientation direction is on the same side as the maximum value in the longitudinal or width direction, and a negative value when the orientation direction is on the opposite side to the longitudinal or width direction. The minimum value is evaluated by distinguishing between positive and negative.
[0199] (2) Refractive index of the transfer alignment film A 4 cm x 2 cm rectangle was cut out so that the slow axis direction determined in (1) above was parallel to the long side, and used as a measurement sample. The refractive indexes of the two perpendicular axes (refractive index in the slow axis direction: nx, refractive index in the fast axis direction (direction perpendicular to the slow axis direction): ny) and the refractive index in the thickness direction (nz) of this sample were determined using an Abbe refractometer (Atago Co., Ltd., NAR-4T, measurement wavelength 589 nm).
[0200] (3) Heat shrinkage rate of the transfer orientation film at 150°C for 30 minutes in the MD direction, TD direction, 45° direction to the MD direction, or 135° direction to the MD direction Measurement was performed in accordance with JIS C 2318-1997 5.3.4 (dimensional change). Specifically, the film was cut to a width of 10 mm and a length of 250 mm in the direction to be measured (MD, TD, 45 degrees to MD, and 135 degrees to MD), and two marks were made on this sample at 200 mm intervals. The distance (A) between the two marks was measured under a constant tension of 5 gf. The film was then placed in an oven in an atmosphere of 150°C, and heat-treated at 150±3°C for 30 minutes under no load, after which the distance (B) between the two marks was measured under a constant tension of 5 gf. The thermal shrinkage was calculated from the following formula. Heat shrinkage rate (%) = (AB) / A x 100
[0201] (4) Maximum heat shrinkage at 95℃ The transfer orientation film cut out from each cut-out portion of the slit roll was cut into a square shape with a side length of 21 cm, and left in an atmosphere of 23°C and 65% RH for more than 2 hours. A circle with a diameter of 80 mm was drawn with the center of the film as the center, and the diameter was measured at 1 degree intervals using a two-dimensional image measuring device (QUICK IMAGE manufactured by MITUTOYO) with the film flow direction set as 0 degrees. Here, the film flow direction was set as 0 degrees, and the clockwise (right-handed) angle was set as a positive angle, and the counterclockwise (left-handed) angle was set as a negative angle on the upper surface of the film. The diameter was measured in all directions in the range of -90 degrees to 89 degrees. Next, the film was heat-treated in hot water at 95°C for 30 minutes, and then left in an atmosphere of 23°C and 65% RH for more than 2 hours. Thereafter, the diameter of the circle was measured at 1 degree intervals in the same manner as above. The diameter before heat treatment was Lo, and the diameter in the same direction after heat treatment was L. The heat shrinkage in each direction was calculated according to the following formula, and the maximum value among the heat shrinkage in all directions was taken as the maximum heat shrinkage. In addition, the angle between the direction with the maximum heat shrinkage and MD or TD (the angle with the smaller value) was calculated. Heat shrinkage rate (%) = ((L0-L) / L0) x 100
[0202] (5) Elastic modulus: Measured according to JIS C-2318. A sample was cut from the center in the width direction of a slit roll obtained by slitting from the center.
[0203] (6) Light transmittance at a wavelength of 380 nm Using a spectrophotometer (Hitachi, U-3500 type), the light transmittance of the alignment film for transfer in the wavelength region of 300 to 500 nm was measured with the air layer as the standard, and the light transmittance at a wavelength of 380 nm was determined.
[0204] (7) Intrinsic viscosity 0.2 g of the resin sample was dissolved in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (60 / 40 (weight ratio)) and measured using an Ostwald viscometer at 30° C. For the sample of surface layer A, layer A alone was extruded to prepare a film sample, which was used as the sample.
[0205] (8) Light leakage A lower polarizing plate was placed on a surface-emitting light source using a white LED with a yellow phosphor as a light source, and a sample laminate in which a retardation layer (liquid crystal compound alignment layer) was provided on an alignment film for transfer was placed on the lower polarizing plate so that the extinction axis direction (absorption axis direction) of the polarizing plate was parallel to the long side direction of the sample laminate. Furthermore, a λ / 4 film made of a stretched film of cyclic polyolefin was placed on the lower polarizing plate so that the orientation main axis was 45 degrees to the extinction axis of the lower polarizing plate, and an upper polarizing plate was placed on the upper polarizing plate so that the extinction axis of the upper polarizing plate was parallel to the extinction axis of the lower polarizing plate. The extinction state was observed in this state. Specifically, the extinction state of the brightest part of the sample laminate was evaluated according to the following criteria. The extinction state was determined as the extinction state in which the lower polarizing plate and the upper polarizing plate were in a cross-Nicol state, except for the sample laminate and the λ / 4 film. ⊚: There was no bright spot and the whole was in a quenched state. ◯: Slightly more transmitted light was observed than in the extinction state. △: Transmitted light was observed, but it was possible to evaluate the phase difference state. ×: There was a large amount of transmitted light, making it difficult to evaluate the phase difference state.
[0206] (9) Brightness uniformity Under the same conditions as in (8) above, the uniformity of the extinction state within the sample laminate was evaluated according to the following criteria: Except for the sample laminate and the λ / 4 film, the extinction state was defined as the state in which the lower polarizing plate and the upper polarizing plate were in a crossed Nicol state. ⊚: The brightness was almost the same over the entire sample laminate. ○: There was a slight difference in brightness. △: There was a small difference in brightness. ×: The difference in brightness was large.
[0207] (10) Thermal alignment deviation of retardation layer The sample laminate was heated in an oven at 120°C for 20 minutes, and a commercially available optical adhesive sheet was attached to the retardation layer side of the sample laminate cooled to room temperature. The adhesive sheet was then attached to a glass plate, and the orientation film was peeled off to transfer the retardation layer onto the glass plate. With the retardation layer laminated on the glass plate, the glass plate / retardation layer laminate was placed between polarizing plates arranged in a crossed Nicol position, and the extinction direction was determined. The angle difference between the extinction direction and the long side direction of the orientation film was determined, and the difference between this angle difference and 45 degrees was taken as the thermal orientation direction deviation. The average value of the values obtained five times was calculated and evaluated according to the following criteria. ◎: Within 1 degree. ○: More than 1 degree, but less than 2 degrees. △: More than 2 degrees, but less than 3 degrees. ×: Over 3 degrees.
[0208] (11) Ester Cyclic Trimer Content The polyester resin constituting the release surface layer of the polyester film was scraped off with a cutter knife and finely frozen and crushed. 0.1 g of this crushed resin was dissolved in 3 ml of a mixed solvent of hexafluoroisopropanol (HFIP) / chloroform (2 / 3 (volume ratio)). 20 ml of chloroform was added to the obtained solution and mixed uniformly. 10 ml of methanol was added to the obtained mixed liquid to reprecipitate the linear polyester. Next, this mixed liquid was filtered, and the precipitate was washed with 30 ml of a mixed solvent of chloroform / methanol (2 / 1 (volume ratio)) and further filtered. The obtained filtrate was concentrated to dryness using a rotary evaporator. 10 ml of dimethylformamide was added to the concentrated and dried product to prepare an ester cyclic trimer measurement solution, and the content of the ester cyclic trimer was determined by liquid chromatography. (Measurement conditions) Equipment: L-7000 (Hitachi) Column: μ-Bondasphere C18 5μ 100 angstroms 3.9mm×15cm (Waters) Solvents: Eluent A: 2% acetic acid / water (v / v) Eluent B: Acetonitrile Gradient B%: 10→100% (0→55 min) Flow rate: 0.8ml / min Temperature: 30℃ Detector: UV-258nm
[0209] (12) Amount of ester cyclic trimer precipitated on the release surface of the film The polyester film was cut to 15cm x 15cm and heated in an oven at 150°C for 90 minutes. The heat-treated film was then placed on a 15cm x 15cm stainless steel plate with the release side facing up, and a 15cm x 15cm silicone sheet (5mm thick) with a 10cm x 10cm hole in the center was placed on top of it, and a stainless steel plate of the same shape (2mm thick) as the silicone sheet was placed on top of it, and the periphery was secured with clips. Next, 4ml of DMF (dimethylsulfamide) was placed in the central hole and left for 3 minutes, after which the DMF was collected. The amount of ester cyclic trimer in the collected DMF was determined by liquid chromatography. This value was divided by the area of the film that was in contact with DMF to determine the amount of ester cyclic trimer precipitated (mg / m2) on the surface of the release side of the film. 2 ) was decided. (Measurement conditions) Equipment: ACQUITY UPLC (Waters) Column: BEH-C18 2.1 x 150 mm (Waters) Mobile phase: Eluent A: 0.1% formic acid (v / v) Eluent B: Acetonitrile Gradient B%: 10→98→98% (0→25→30 min) Flow rate: 0.2ml / min Column temperature: 40℃ Detector: UV-258nm
[0210] (13) Evaluation of haze increase (△ haze) before and after heat treatment The film was cut into a 50mm x 75mm square, and the initial haze (pre-heating haze) before heat treatment was measured in accordance with JIS K 7105 "Testing Methods for Optical Properties of Plastics" haze (cloudiness value). The measurement device used was a Nippon Denshoku Industries NDH-300A turbidity meter. To measure the post-heating haze, a protective film (Fujimori Kogyo PC-T073) was attached to the side (back side) of the sample film that was not evaluated for haze before heat treatment using a roller to prevent air bubbles from being trapped. The film with the protective film attached was placed in an oven heated to 150°C, and the film was removed after 90 minutes. The protective film was then peeled off, and the haze of the film was measured in the same manner as above to obtain the post-heating haze. The difference in haze before and after heating was taken as △ haze. ΔHaze (%) = (Haze after heating) - (Haze before heating)
[0211] (14) Surface resistivity of polyester film (Ω / sq) According to JIS K 6911, the surface resistivity (Ω) was measured using a surface resistivity measuring device (manufactured by Takeda Riken Co., Ltd.) in an atmosphere of 23° C. and 40% RH at an applied voltage of 500 V.
[0212] (15) Suitable for high-speed coating The solution for forming the retardation layer was applied to the uncoated side or the oligomer block coated side of the transfer orientation film using a gravure coater and dried. After that, the film quality near the core of the transfer orientation film (around 450 m from the start) was observed and evaluated according to the following criteria. A: The coating film was uniform. ×: Cracks thought to be due to static electricity were observed.
[0213] (16) Three-dimensional surface roughness SRa, SRz, SRy Using a stylus-type three-dimensional roughness meter (SE-3AK, manufactured by Kosaka Laboratory Co., Ltd.), measurements were taken over a measurement length of 1 mm with a cutoff value of 0.25 mm in the longitudinal direction of the film under conditions of a needle radius of 2 μm and a load of 30 mg, with a needle feed speed of 0.1 mm / sec., and the film was divided into 500 points at a pitch of 2 μm, and the height of each point was recorded in a three-dimensional roughness analyzer (SPA-11). The same operation was performed continuously 150 times at intervals of 2 μm in the width direction of the film, that is, over a width of 0.3 mm in the width direction of the film, and the data was recorded in the analyzer. Next, the center surface average roughness (SRa), ten-point average roughness (SRz), and maximum height (SRy) were determined using the analyzer.
[0214] (17) The number of protrusions on the release surface with a height difference of 0.5 μm or more (release surface) and 2.0 μm or more (reverse surface) A test piece with a width of 100 mm and a length of 100 mm was cut out in the longitudinal direction of the film, and this was sandwiched between two polarizing plates in a cross-Nicol state, and set in a state where the extinction position was maintained. In this state, a Nikon universal projector V-12 (measurement conditions: projection lens 50x, transmitted illumination light beam switching knob 50x, transmitted light inspection) was used to detect parts (scratches, foreign bodies) with a major axis of 50 μm or more through which light was transmitted and which appeared to be shiny. The parts thus detected were cut out to an appropriate size from the test piece, and observed and measured from a direction perpendicular to the film surface using a three-dimensional shape measuring device (manufactured by Ryoka Systems, Micromap TYPE 550; measurement conditions: wavelength 550 nm, WAVE mode, objective lens 10x). At this time, when observed from a direction perpendicular to the film surface, irregularities that are close to each other within 50 μm are assumed to be the same scratches or foreign bodies, and a rectangle that covers them is assumed to be the length and width of the rectangle. The number of defects was quantified using cross-sectional images (SURFACE PROFILE DISPLAY) for these scratches and foreign bodies. 2 The number of defects with a height difference (difference between the highest and lowest points) of 0.5 μm or more on the release surface was counted, and the number of defects with a height difference of 2.0 μm or more on the back surface was counted.
[0215] <Production of polyester resin for transfer orientation film> (Manufacture of polyester resin (PET(Xm))) When the temperature of the esterification reactor reached 200°C, 86.4 parts by mass of terephthalic acid and 64.6 parts by mass of ethylene glycol were charged, and 0.017 parts by mass of antimony trioxide, 0.064 parts by mass of magnesium acetate tetrahydrate, and 0.16 parts by mass of triethylamine were charged as catalysts while stirring. Next, the temperature was increased under pressure, and a pressurized esterification reaction was carried out under conditions of a gauge pressure of 0.34 MPa and 240°C, after which the esterification reactor was returned to normal pressure and 0.014 parts by mass of phosphoric acid was added. Further, the temperature was increased to 260°C over 15 minutes, and 0.012 parts by mass of trimethyl phosphate was added. Next, after 15 minutes, a dispersion treatment was carried out using a high-pressure disperser, and after 15 minutes, the obtained esterification reaction product was transferred to a polycondensation reactor and a polycondensation reaction was carried out under reduced pressure at 280°C.
[0216] After the polycondensation reaction was completed, the mixture was filtered through a Naslon filter with a 95% cut diameter of 5 μm, extruded from a nozzle in the form of a strand, cooled and solidified using cooling water that had been previously filtered (pore diameter: 1 μm or less), and cut into pellets to obtain a polyethylene terephthalate resin (PET(Xm)). The intrinsic viscosity of PET(Xm) was 0.62 dl / g, and it contained substantially no inert particles or internally precipitated particles.
[0217] (Preparation of Polyester Resin (PET(Y)) 10 parts by mass of dried ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one) and 90 parts by mass of PET(Xm) (intrinsic viscosity: 0.62 dl / g) were mixed and kneaded using an extruder to obtain polyethylene terephthalate resin (PET(Y)) containing an ultraviolet absorber.
[0218] (Production of low oligomer polyester (Xs)) The polyester resin (PET(Xm)) was dried at 160°C under reduced pressure and then the water content was determined to be 15.3g / Nm 3Nitrogen gas with a humidity control was passed through the crude polyester at a rate of 300 L / hour per 1 kg of the crude polyester, and the polyester was heat-treated for 12 hours at 230° C. The intrinsic viscosity of the resulting polyester was 0.617 dl / g, and the content of cyclic trimer was 0.29% by mass.
[0219] <Production of Easy-Adhesion Layer Component> (Production of polyurethane resin D-1) A polyurethane resin D-1 containing an aliphatic polycarbonate polyol as a constituent component was produced by the following procedure. 43.75 parts by mass of 4,4-diphenylmethane diisocyanate, 12.85 parts by mass of dimethylol butanoic acid, 153.41 parts by mass of polyhexamethylene carbonate diol having a number average molecular weight of 2000, 0.03 parts by mass of dibutyltin dilaurate, and 84.00 parts by mass of acetone as a solvent were added to a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, and the mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction solution reached a predetermined amine equivalent. Next, the reaction solution was cooled to 40°C, and then 8.77 parts by mass of triethylamine was added to obtain a polyurethane prepolymer solution. Next, 450g of water was added to a reaction vessel equipped with a homodisperser capable of high speed stirring, and the temperature was adjusted to 25°C. The polyurethane prepolymer solution was added and dispersed in water while stirring and mixing at 2000 min-1. Then, acetone and a part of the water were removed under reduced pressure to prepare a water-soluble polyurethane resin (D-1) with a solid content concentration of 35 mass%. The glass transition temperature of the obtained polyurethane resin (D-1) was -30°C.
[0220] (Production of oxazoline-based crosslinking agent E-1) A mixture of 58 parts by mass of ion-exchanged water and 58 parts by mass of isopropanol as an aqueous medium, and 4 parts by mass of a polymerization initiator (2,2'-azobis(2-amidinopropane) dihydrochloride) were placed in a flask equipped with a thermometer, a nitrogen gas inlet tube, a reflux condenser, a dropping funnel, and a stirrer. Meanwhile, a mixture of 16 parts by mass of 2-isopropenyl-2-oxazoline as a polymerizable unsaturated monomer having an oxazoline group, 32 parts by mass of methoxypolyethylene glycol acrylate (average number of moles of ethylene glycol added: 9 moles, Shin-Nakamura Chemical Co., Ltd.), and 32 parts by mass of methyl methacrylate were placed in the dropping funnel, and added dropwise at 70°C for 1 hour under a nitrogen atmosphere. After the dropwise addition was completed, the reaction solution was stirred for 9 hours and cooled to obtain a water-soluble resin (E-1) having an oxazoline group with a solid content of 40% by mass.
[0221] (Preparation of Coating Solution for Adhesion Layer) The following coating materials were mixed to prepare a coating solution for an easy-adhesion layer. Water 55.62% by mass Isopropanol 30.00% by mass Polyurethane resin (D-1) 11.29% by mass Oxazoline-based crosslinking agent (E-1) 2.26% by mass Particles 0.71% by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Particles 0.07% by mass (Silica sol with average particle size of 450 nm, solid content concentration of 40% by mass) Surfactant: 0.05% by mass (Silicone-based, solid content 100% by mass) (Solid content concentration 10% by mass)
[0222] (Manufacture of Transfer Orientation Film Roll 1) As the raw material for the intermediate layer of the transfer oriented film, 90 parts by mass of PET (Xm) resin pellets and 10 parts by mass of PET (Y) resin pellets containing an ultraviolet absorber were dried under reduced pressure (1 Torr) at 135 ° C for 6 hours, and then fed to extruder 2 (for intermediate layer II layer). In addition, as the raw material for the outer layer of the transfer oriented film, PET (Xm) was dried by a conventional method and fed to extruder 1 (for outer layer (I layer, III layer)) and melted at 285 ° C. These two types of polymers were each filtered with a stainless steel sintered filter medium (nominal filtration accuracy 10 μm particle 95% cut), laminated in a two-type three-layer merging block, extruded from a die in the form of a sheet, and then wound around a casting drum with a surface temperature of 30 ° C. using an electrostatic casting method, cooled and solidified, and an unstretched film was made. At this time, the discharge amount of each extruder was adjusted so that the thickness ratio of I layer, II layer, and III layer was 10:80:10.
[0223] Next, a coating solution for easy adhesion was applied to one side of the unstretched PET film by the reverse roll method so that the coating amount after drying was 0.08 g / m 2 After coating so that the coating was applied, the coating was introduced into a dryer and dried at 80° C. for 20 seconds.
[0224] The unstretched film with the coating layer formed thereon was introduced into a tenter stretching machine, and while the ends of the film were held by clips, the film was introduced into a hot air zone at a temperature of 125°C and stretched 4.0 times in the width direction. Next, while maintaining the width stretched in the width direction, the film was heat-set at a temperature of 210°C for 10 seconds, and further relaxed by 3.0%. Then, both ends of the cooled film were cut and the film was cooled to 0.4 kg / mm 2 The film was taken up with a tension of 1000 .mu.m to obtain a uniaxially oriented PET film (width 1800 cm, transfer orientation film 1) with a film thickness of 50 .mu.m. The central portion of the obtained film was slit into a width of 50 cm to obtain a film roll (slit film 1-c) having a length of about 500 m. The obtained film was slit to a width of 50 cm on the right side from the center to obtain a film roll (1-r1) having a length of approximately 500 m. The right end of the obtained film was slit to a width of 50 cm to obtain a film roll (1-r2) having a length of approximately 500 m.
[0225] (Manufacture of Transfer Orientation Film Roll 2) An unstretched film (coated with an easy-adhesion layer) prepared in the same manner as transfer oriented film 1 was heated to 105°C using a group of heated rolls and an infrared heater, and then stretched 3.3 times in the running direction using a group of rolls with different peripheral speeds.It was then introduced into a hot air zone at a temperature of 135°C and stretched 3.5 times in the width direction. Transfer oriented film 2 was obtained in the same manner as transfer oriented film 1, except that the heat setting temperature was set to 225°C. The central portion of the obtained film was slit to a width of 50 cm to obtain a film roll (2-c) having a length of about 500 m. The obtained film was slit to a width of 50 cm on the right side from the center to obtain a film roll (2-r1) having a length of about 500 m. The resulting film was slit in a width of 50 cm at the center of the right half to obtain a film roll (2-r2) having a length of approximately 500 m. The right end of the obtained film was slit to a width of 50 cm to obtain a film roll (2-r3) having a length of approximately 500 m.
[0226] (Manufacture of Transfer Orientation Film Roll 3-c) The film roll 1-c was unwound, passed through a heating oven at 130° C., taken up, and annealed to obtain an orientation film roll 3-c for transfer. The time of passing through the oven was 20 seconds.
[0227] (Manufacture of transfer orientation film roll 4-c) The same procedure as for the transfer orientation film 1 was carried out to obtain a transfer orientation film roll 4-c, except that the relaxation treatment conditions were changed as shown in Table 1. The central portion was slit.
[0228] (Manufacture of Transfer Orientation Film Roll 5-c) The same procedure as for the transfer orientation film 1 was carried out to obtain a transfer orientation film roll 5-c, except that the heat setting temperature was changed as shown in Table 1. The central portion was slit.
[0229] (Manufacture of Transfer Orientation Film Roll 6-c) The same procedure as for the transfer orientation film 1 was carried out to obtain a transfer orientation film roll 6-c, except that the stretching ratio in the width direction was changed as shown in Table 1. The central portion was slit.
[0230] (Manufacture of Transfer Orientation Film Roll 7-c) The transfer orientation film roll 6-c was subjected to an annealing treatment to obtain a transfer orientation film roll 7-c.
[0231] (Manufacture of Transfer Orientation Film Roll 8-c) An unstretched film (coated with an easy-adhesion layer) produced in the same manner as in transfer orientation film 1 was heated to 105°C using a heated roll group and an infrared heater, then stretched 2.0 times in the running direction using a roll group with different peripheral speeds, and then introduced into a hot air zone at a temperature of 135°C and stretched 4.0 times in the width direction to obtain transfer orientation film roll 8-c in the same manner as in transfer orientation film 1. The center part was slit.
[0232] (Manufacture of Transfer Orientation Film Roll 9-c) The heat setting temperature was 170°C, no relaxation treatment was performed, and the strain rate was 0.6 kg / mm 2 The film was wound up under a tension of 1.0 mm, and the film was then wound up under the same conditions as in the case of the film 1, to obtain a film roll 9-c. The central portion was slit.
[0233] (Manufacture of Transfer Orientation Film Roll 10-c) An unstretched film (coated with an easy-adhesion layer) prepared in the same manner as the transfer orientation film 1 was heated to 105°C using a heated roll group and an infrared heater, then stretched 4.0 times in the running direction using a roll group with a difference in peripheral speed, and then processed in a dryer at a temperature of 225°C for 10 seconds, and relaxed 3.0% using the difference in peripheral speed to obtain a transfer orientation film roll 10-c. The center part was slit. In the above-mentioned transfer orientation film rolls 1 to 10-c, the surface on which no easy-adhesion layer was applied (non-easy-adhesion coating layer surface) was used as the release surface.
[0234] (Manufacture of Transfer Orientation Film Roll 11-c) The non-adhesive coated surface of the transfer orientation film roll 1 (1-c) was subjected to corona treatment, and the following oligomer block coating agent was applied thereto, and the coating was dried in a heating oven at 150°C for 3 minutes to obtain a transfer orientation film roll 11-c. The coating layer had a thickness of 150 nm. Melamine cross-linked alkyl-modified alkyd resin (Hitachi Chemical Polymer Co., Ltd.: Tesfine 322: solids content 40%) 2.5 parts P-Toluenesulfonic acid (Hitachi Chemical Polymers: Dryer 900) 0.025 parts Toluene 50 parts Methyl ethyl ketone 47.2 parts The oligomer block coat layer surface was used as a release surface.
[0235] (Manufacture of Transfer Orientation Film Roll 12-c) The same procedure was carried out as for the transfer orientation film 1, except that the following coating agent (oligomer block coating agent) was used instead of the coating solution for the easy-adhesion layer on one side, and the following coating agent not containing silica particles was used on the other side, to obtain a transfer orientation film roll 12-c. The center part was slit. Hexamethoxymethylolmelamine 52% by weight Epocross (manufactured by Nippon Shokubai Co., Ltd.). Oxazoline group amount: 7.7mmol / g 30% by mass Polyglycerol polyglycidyl ether 10% by mass 2-Amino-2-methylpropanol hydrochloride 3% by mass Silica particles (average particle size 0.07 μm) 5% by mass (Solvent: toluene / MEK=1 / 1) The surface of the oligomer block coat layer not containing silica particles was used as a release surface.
[0236] (Manufacture of Transfer Orientation Film Roll 13-c) The same procedure as for the transfer orientation film roll 11-c was carried out except that PET(Xs) was used instead of PET(Xm), to obtain a transfer orientation film roll 13-c. The central portion was slit. The oligomer block coat layer surface was used as a release surface.
[0237] (Manufacture of Transfer Orientation Film Roll 14-c) The same procedure was carried out as for the transfer orientation film 1, except that the following coating agent was used as the coating liquid for the easy-adhesion layer, to obtain a transfer orientation film roll 14-c having antistatic properties. Water 16.70% by mass Isopropanol 21.69% by mass Sorbitol 5.00% by mass Thiophene resin 51.02% by mass (Bytron P AG manufactured by Starck, solid content concentration 1.2% by mass) Polyurethane resin (D-1) 3.81% by mass Oxazoline-based crosslinking agent aqueous solution (E-1) 1.22% by mass Particles 0.70% by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Particles 0.07% by mass (Silica sol with average particle size of 450 nm, solid content concentration of 40% by mass) Surfactant: 0.05% by mass (Silicone-based, solid content 100% by mass) (Solid content concentration 10% by mass) The non-adhesive coating layer surface was used as a release surface.
[0238] (Manufacture of Transfer Orientation Film Roll 15-c) On the adhesive coating surface of the transfer orientation film roll 1 (1-c), Pertron C-4402 (antimony-doped tin oxide particles) was applied in MEK at a solid content concentration of 5%, and dried in a heating oven at 80°C for 3 minutes to provide an antistatic coating layer with a thickness of 100 nm. On the other hand, on the non-adhesive coating surface, an oligomer block coating layer was provided in the same manner as in the transfer orientation film 11-c, to obtain a transfer orientation film roll 15-c having antistatic properties. The oligomer block coat layer surface was used as a release surface.
[0239] Table 1 shows the manufacturing conditions and characteristics of each of the above transfer orientation film rolls. [Table 1]
[0240] Experimental Example 1A (Formation of rubbing treatment alignment control layer) The transfer alignment film roll 1-c was unwound and cut into a length of 30 cm, and the non-adhesive coated surface was coated with a coating material for a rubbing treatment alignment control layer having the following composition using a bar coater, and dried at 80°C for 5 minutes to form a film with a thickness of 200 nm. The surface of the obtained film was then treated with a rubbing roll wrapped with a nylon nap cloth to obtain a transfer alignment film laminated with a rubbing treatment alignment control layer. Rubbing was performed at an angle of 45 degrees to the short side of the cut-out rectangle. Fully saponified polyvinyl alcohol (weight average molecular weight 800) 2 parts by weight Ion-exchanged water 100 parts by weight Surfactant 0.5 parts by weight
[0241] Subsequently, a solution for forming a retardation layer (liquid crystal compound alignment layer) having the following composition was applied to the rubbed surface by a bar coating method. It was dried at 110°C for 3 minutes and cured by irradiation with ultraviolet light to form a λ / 4 layer as a retardation layer (liquid crystal compound alignment layer) on the alignment film for transfer 1-c, thereby producing a laminate for transferring the alignment layer for liquid crystal compounds. Rod-shaped liquid crystal compound (BASF LC242) 75 parts by weight The following compound: 20 parts by weight TIFF2024170606000004.tif1590 Trimethylolpropane triacrylate 5 parts by mass Irgacure 379 3 parts by weight Surfactant 0.1 parts by weight Methyl ethyl ketone 250 parts by mass
[0242] Experimental Examples 2A, 3A, 6A-21A, Experimental Example 2B Except for changing the type of the alignment film for transfer as shown in Table 2, laminates for transferring a liquid crystal compound alignment layer of Experimental Examples 2A, 3A, 6A to 21A, and 2B were produced in the same manner as in Experimental Example 1A.
[0243] Experimental Examples 4A, 5A, and 1B The transfer alignment film roll 1-r2 was cut to a length of about 30 cm, and the cut film was shaped into a rectangle of as large an area as possible so that the angles between the alignment axis of the film and the long side direction were 6 degrees, 9 degrees, and 15 degrees. Except for using this film, the laminates for transferring the liquid crystal compound alignment layer of Experimental Examples 4A, 5A, and 1B were produced in the same manner as Experimental Example 3A.
[0244] Table 2 shows the evaluation results of the laminates for transferring a liquid crystal compound alignment layer of Experimental Examples 1A to 21A, 1B, and 2B. Note that the numerical values in the item "Angle between MD or TD and alignment direction (maximum degree)" of Experimental Examples 4A, 5A, and 1B in Table 2 indicate the angle between the long side of the rectangular sample and the alignment axis. [Table 2]
[0245] As is clear from Table 2, all of Experimental Examples 1A to 21A, which satisfy the requirements of the first invention, had light leakage of ◎, ○, or △, and it was possible to evaluate the retardation state in a state where the retardation layer (liquid crystal compound alignment layer) was laminated on the alignment film, and the brightness uniformity was also excellent. In contrast, all of Experimental Examples 1B and 2B, in which the angle between the alignment direction of the alignment film and the flow direction of the alignment film or the direction perpendicular to the flow direction is too large, had light leakage of ×, and it was difficult to evaluate the retardation state in a state where the retardation layer (liquid crystal compound alignment layer) was laminated on the alignment film.
[0246] Also, as is clear from Table 2, in all of Experimental Examples 1A to 3A, 6A to 14A, and 16A to 21A, which satisfy the requirements of the second invention, the orientation angle deviation of the retardation layer was ◎, ○, or △. In contrast, in Experimental Example 15A, in which the difference in 150°C heat shrinkage rate between the flow direction (MD direction) of the oriented film and the direction perpendicular to the flow direction (TD direction) was too large, the orientation angle deviation of the retardation layer was ×. In the case of Experimental Example 15A, if further heat is applied in the next process or the temperature when the retardation layer is provided becomes high, the orientation direction of the retardation layer may be shifted, and it may not be possible to provide a retardation layer with the designed orientation on the target object.
[0247] Table 3 shows the effects of the oligomer block coat and the antistatic layer of the laminates for transferring a liquid crystal compound alignment layer of Experimental Examples 17A to 21A in comparison with Experimental Example 1A. [Table 3]
[0248] As is clear from Table 3, all of the experimental examples 17A to 19A, which satisfy the requirements of the third invention, had a small Δhaze (the increase in haze before and after heat treatment), and the increase in haze due to heat treatment was sufficiently suppressed. In particular, experimental example 19A, which used a polyester with a low oligomer content as the polyester resin constituting the oriented film, had a small surface oligomer content and therefore a small amount of surface oligomer precipitation, and as a result, the Δhaze was significantly smaller than that of the other examples, and the increase in haze due to heat treatment was extremely sufficiently suppressed. In contrast, experimental example 1A, which had a large amount of surface oligomer precipitation, had a large Δhaze, and the haze was significantly increased by the heat treatment. In addition, both experimental example 21A, which had an antistatic coating layer, and experimental example 20A, which had an antistatic agent added to the easy-adhesion layer, had sufficiently low surface resistance of the film and excellent antistatic properties compared to experimental example 1A, which did not have such a thing.
[0249] As a representative example, the surface roughness of the film of Experimental Example 1A is shown in Table 4. In addition, in the evaluation of the retardation layer, no defects such as pinholes or scratches were found. [Table 4]
[0250] Example 22A (Production of a circular polarizing plate as a specific example of a liquid crystal compound alignment layer laminated polarizing plate) A 100 μm-thick unstretched film was prepared using polyethylene terephthalate with an intrinsic viscosity of 0.63 as a thermoplastic resin substrate, and an aqueous solution of polyvinyl alcohol with a degree of polymerization of 2400 and a degree of saponification of 99.9 mol% was applied to one side of the unstretched film and dried to form a PVA layer. The obtained laminate was stretched twice in the longitudinal direction between rolls with different peripheral speeds at 120° C. and wound up. Next, the obtained laminate was treated with a 4% boric acid aqueous solution for 30 seconds, and then immersed in a mixed aqueous solution of iodine (0.2%) and potassium iodide (1%) for 60 seconds to dye it, and subsequently treated with a mixed aqueous solution of potassium iodide (3%) and boric acid (3%) for 30 seconds. Furthermore, this laminate was uniaxially stretched in the longitudinal direction in a mixed aqueous solution of boric acid (4%) and potassium iodide (5%) at 72°C, then washed with a 4% aqueous solution of potassium iodide, the aqueous solution was removed with an air knife, and then dried in an oven at 80°C. Both ends were slit and wound up to obtain a substrate-laminated polarizer with a width of 30 cm and a length of 1000 m. The total stretching ratio was 6.5 times, and the thickness of the polarizer was 5 μm. The thickness was measured by embedding the substrate-laminated polarizer in epoxy resin, cutting out a slice, and observing it with an optical microscope.
[0251] The polarizer surface of the substrate-laminated polarizer was attached to a super-birefringent polyester film (Cosmoshine (R) SRF, thickness 80 μm, manufactured by Toyobo Co., Ltd.) using an ultraviolet-curing adhesive, and then the substrate of the substrate-laminated polarizer was peeled off. Furthermore, a commercially available optical adhesive sheet was laminated on the polarizer surface. The release film of the adhesive sheet was peeled off, and the liquid crystal compound alignment layer surface of the laminate for transferring the liquid crystal compound alignment layer of Experimental Example 1A and the adhesive layer were attached to each other, and then the alignment film in the laminate of Experimental Example 1A was peeled off to obtain a circular polarizing plate. The obtained circular polarizing plate had a high anti-reflection function. The slow axis of Cosmoshine (R) SRF and the extinction axis of the polarizer were perpendicular to each other, and the MD direction of Cosmoshine (R) SRF and the MD direction of the alignment film in the laminate of Experimental Example 1A were parallel to each other. [Industrial Applicability]
[0252] The alignment film for transferring a liquid crystal compound alignment layer of the present invention can appropriately evaluate the alignment state of the liquid crystal compound alignment layer (retardation layer or polarizing layer) provided thereon in a state in which the liquid crystal compound alignment layer is laminated on the alignment film. In addition, the alignment film for transferring a liquid crystal compound alignment layer of the present invention can transfer a retardation layer or a polarizing layer with the designed orientation while using a stretched film such as polyester that is inexpensive and has excellent mechanical strength, and can prevent the problem of light leakage in the display. Furthermore, the alignment film for transferring a liquid crystal compound alignment layer of the present invention can effectively prevent an increase in haze and the generation of foreign matter during the heat treatment of the film while using a stretched film such as polyester that is inexpensive and has excellent mechanical strength, and can form a retardation layer or a polarizing layer (liquid crystal compound alignment layer) with the designed orientation. Therefore, according to the present invention, a retardation layer-laminated polarizing plate such as a circular polarizing plate can be stably manufactured with high quality.
Claims
1. A long laminate in which a liquid crystal compound alignment layer and an alignment film are laminated, The oriented film has an angle between the orientation direction of the oriented film and the flow direction of the oriented film or a direction perpendicular to the flow direction of the oriented film, the maximum angle being 14 degrees or less among the values measured at five locations: both ends 5 cm inward from each end in the width direction of the film, the center, and a middle portion between the center and both ends; and The haze of the oriented film is 3% or less; The laminate is a long laminate for transferring an alignment layer for a liquid crystal compound, which is obtained by any one of the following methods (A) to (D). (A) a step of rubbing an alignment film to impart an alignment control function; A process of providing a liquid crystal compound alignment layer on an alignment film provided with an alignment control function. in that order; (B) applying a liquid crystal compound onto the alignment film; A process in which the liquid crystal compound is irradiated with polarized light to align the liquid crystal compound, forming a liquid crystal compound alignment layer. in that order; (C) preparing an oriented film; providing an orientation control layer on the orientation film; a step of rubbing the alignment control layer to provide an alignment control function; A step of providing a liquid crystal compound alignment layer on the alignment control layer in that order; (D) preparing an oriented film; providing an orientation control layer on the orientation film; a step of irradiating the alignment control layer with polarized light to impart an alignment control function; A step of providing a liquid crystal compound alignment layer on the alignment control layer A method that includes, in this order.
2. A long laminate in which a liquid crystal compound alignment layer and an alignment film are laminated, The oriented film is a long laminate for transferring a liquid crystal compound alignment layer, in which the angle between the orientation direction of the oriented film and the flow direction of the oriented film or the direction perpendicular to the flow direction is 14 degrees or less as the maximum value measured at five locations: both ends 5 cm inward from each end in the width direction of the film, the center, and a middle portion halfway between the center and both ends, and the haze of the oriented film is 3% or less (excluding the case where the liquid crystal compound alignment layer contains a chiral agent).
3. 3. The long laminate for transferring a liquid crystal compound alignment layer according to claim 2, wherein the laminate is obtained by any one of the following methods (A) to (D). (A) a step of rubbing an alignment film to impart an alignment control function; A process of providing a liquid crystal compound alignment layer on an alignment film provided with an alignment control function. in that order; (B) applying a liquid crystal compound onto the alignment film; A process in which the liquid crystal compound is irradiated with polarized light to align the liquid crystal compound, forming a liquid crystal compound alignment layer. in that order; (C) preparing an oriented film; providing an orientation control layer on the orientation film; a step of rubbing the alignment control layer to provide an alignment control function; A step of providing a liquid crystal compound alignment layer on the alignment control layer in that order; (D) preparing an oriented film; providing an orientation control layer on the orientation film; a step of irradiating the alignment control layer with polarized light to impart an alignment control function; A step of providing a liquid crystal compound alignment layer on the alignment control layer A method that includes, in this order.
4. 4. The long laminate for transferring a liquid crystal compound alignment layer according to claim 1, wherein the difference in the alignment angle in the width direction of the alignment film is 7 degrees or less. The difference in the orientation angle in the width direction of the film is the difference between the maximum and minimum angles among the angles obtained at the above five locations, and the angle is taken as a positive value if the orientation direction is on the same side as the maximum value in the longitudinal or width direction, and a negative value if the orientation direction is on the opposite side to the longitudinal or width direction, and the minimum value is obtained by distinguishing between positive and negative.
5. The laminate for transferring a liquid crystal compound alignment layer according to any one of claims 1 to 4, characterized in that the difference between the heat shrinkage rate at 150°C for 30 minutes in the machine direction of the alignment film and the heat shrinkage rate at 150°C for 30 minutes in the direction perpendicular to the machine direction of the alignment film is 4% or less.
6. The laminate for transferring a liquid crystal compound alignment layer according to any one of claims 1 to 5, characterized in that the difference between the heat shrinkage rate at 150°C for 30 minutes in a direction at 45° to the machine direction of the alignment film and the heat shrinkage rate at 150°C for 30 minutes in a direction at 135° to the machine direction of the alignment film is 4% or less.
7. 7. The laminate for transferring an alignment layer for a liquid crystal compound according to claim 1, wherein the alignment film is a polyester film.
8. preparing a long oriented film in which the angle between the orientation direction of the oriented film and the flow direction or a direction perpendicular to the flow direction of the oriented film is 14 degrees or less as the maximum value among values measured at five points, namely, both ends 5 cm inward from each end in the width direction of the film, a central portion, and a middle portion between the central portion and both ends, and the haze is 3% or less; A step of providing a liquid crystal compound alignment layer on at least one surface of the alignment film by any one of the following methods (A) to (D): The present invention relates to a method for producing a long liquid crystal compound laminate having the above structure. (A) a step of rubbing an alignment film to impart an alignment control function; A process of providing a liquid crystal compound alignment layer on an alignment film provided with an alignment control function. in that order; (B) applying a liquid crystal compound onto the alignment film; A process in which the liquid crystal compound is irradiated with polarized light to align the liquid crystal compound, forming a liquid crystal compound alignment layer. in that order; (C) preparing an oriented film; providing an orientation control layer on the orientation film; a step of rubbing the alignment control layer to provide an alignment control function; A step of providing a liquid crystal compound alignment layer on the alignment control layer in that order; (D) preparing an oriented film; providing an orientation control layer on the orientation film; a step of irradiating the alignment control layer with polarized light to impart an alignment control function; A step of providing a liquid crystal compound alignment layer on the alignment control layer A method that includes, in this order.
9. preparing a long oriented film in which the angle between the orientation direction of the oriented film and the flow direction or a direction perpendicular to the flow direction of the oriented film is 14 degrees or less as the maximum value among values measured at five points, namely, both ends 5 cm inward from each end in the width direction of the film, a central portion, and a middle portion between the central portion and both ends, and the haze is 3% or less; providing a liquid crystal compound alignment layer on at least one surface of the alignment film; (However, the liquid crystal compound alignment layer does not contain a chiral agent)
10. The step of providing a liquid crystal compound alignment layer comprises: The method for producing a long liquid crystal compound laminate according to claim 9, further comprising the step of providing a liquid crystal compound alignment layer on at least one surface of the alignment film by any one of the following methods (A) to (D): (A) a step of rubbing an alignment film to impart an alignment control function; A process of providing a liquid crystal compound alignment layer on an alignment film provided with an alignment control function. in that order; (B) applying a liquid crystal compound onto the alignment film; A process in which the liquid crystal compound is irradiated with polarized light to align the liquid crystal compound, forming a liquid crystal compound alignment layer. in that order; (C) preparing an oriented film; providing an orientation control layer on the orientation film; a step of rubbing the alignment control layer to provide an alignment control function; A step of providing a liquid crystal compound alignment layer on the alignment control layer in that order; (D) preparing an oriented film; providing an orientation control layer on the orientation film; a step of irradiating the alignment control layer with polarized light to impart an alignment control function; A step of providing a liquid crystal compound alignment layer on the alignment control layer A method that includes, in this order.